Thermal kinetics of biochar-ethylene vinyl acetate for waste-to-energy: Particle swarm optimization, cloud computing, and artificial intelligence - Wei-Hsin Chen; Che-An Lin; Partha Pratim Biswas; Chih-Chun Chen; Biqing Liang; Sheng-Lun Lin; Hwai Chyuan Ong; Aristotle T. Ubando (Fuel, 2026)

CRISPR/Cas9-mediated miR-21 editing in high-grade urothelial carcinoma cells and its biological effects - Maria Carolina Yi Lin Lee; Juliana Alves Camargo; Giovana Caetano Vilas Boas; Karina Serafim Silva; Luana Pereira Silva; Carolina Mie Mioshi; Ruan Pimenta; Iran Amorim Silva; Katia Ramos Moreira Leite; William Carlos Nahas; Sabrina T dos Reis (Molecular Biology Reports, 2026)
Background Urothelial carcinoma, the predominant form of bladder cancer, represents a global public health challenge due to its high rates of recurrence and progression. At the molecular level, microRNA-21 (miR-21) has been characterized as an “oncomir” because of its ability to negatively regulate tumor suppressor genes, thereby promoting tumor survival and progression. In this context, the CRISPR/Cas9 system has emerged as a precise genome-editing tool. Objective To investigate the biological effects of miR-21 modulation using CRISPR/Cas9-mediated genome editing in the T24 high-grade invasive urothelial carcinoma cell line. Methods The CRISPR/Cas9 system was delivered as a ribonucleoprotein (RNP) complex. Editing efficiency was assessed using quantitative reverse transcription PCR (RT-qPCR). Functional effects were evaluated through gene expression assays, cell migration assays, as well as Matrigel invasion assays. The presence of the Cas9 protein was confirmed by immunofluorescence. Results CRISPR/Cas9 treatment targeting miR-21 showed a trend toward reduced miR-21 expression (p = 0.0563), although this did not reach statistical significance. A statistically significant increase in MASPIN (p < 0.0001) and PDCD4 (p = 0.0239), as well as a trend toward increased PTEN expression (p = 0.055), was observed following treatment. Functionally, a significant reduction in the migratory capacity of edited cells was observed after 48 h (p = 0.0334). The presence of Cas9 was successfully confirmed in transfected cells. Conclusion These findings suggest that CRISPR/Cas9-mediated modulation of miR-21 may influence tumor suppressor pathways and reduce the migratory potential of urothelial carcinoma cells.

Future directions in oil spill modeling - Tor Nordam; Ana J. Abascal; Germán Aragón; Hossein Babaei; Christopher H. Barker; Kuo-Hsien Chang; Knut-Frode Dagestad; Rodrigo Duran; Deborah French-McCay; Melissa Gloekler; Aurelien Hospital; Panagiota Keramea; et al. (Ocean Modelling, 2026)

Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

A non‑natural shortcut biosynthetic route enables de novo microbial production of 3‑hydroxyanthranilic and quinolinic acids - Nguyen N. T. Luu; Cui Guo; Ashley Tseng; Yuheng Lin (World Journal of Microbiology and Biotechnology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Outbreak of Salmonella Typhimurium ST19 linked to passerine birds and cats in Norway, March to July 2024 - Hilde Marie Lund; Lin T. Brandal; Liz Ertzeid Ødeskaug; Heidi Lange; Polina Katsiouleri; Gro S. Johannessen; Bjarne Bergsjø; Åsne Sangolt; Rikard Dryselius; Nadja Karamehmedovic; Henry Kuronen; Anni Vainio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose In June 2024, a genomic cluster of seven Salmonella Typhimurium - sequence type 19, and cluster type 21092 - was detected in Norway, triggering a national outbreak investigation. Methods Information about new cases was collected from the Norwegian Surveillance System for Communicable Diseases and the database at the National Reference Laboratory for Enteropathogenic Bacteria (NRL) at the Norwegian Institute of Public Health (NIPH). Microbiological analyses were conducted by NRL at NIPH for human samples and at the Norwegian Veterinary Institute for animal samples. Epidemiological data was collected through interviews. International notification was sent via EpiPulse. Results Eleven cases in total, sampled between March 6 and July 11, 2024, were identified across Norway. The median age of affected individuals was three years. Notably, 73% of the cases reported prior contact with cats or passerine birds. The outbreak strain was also detected in a faecal sample from a cat belonging to one of the affected households, suggesting an animal source. Concurrently, Finland and Sweden reported five and six cases, respectively, involving the same outbreak strain. Several of these individuals also reported contact with cats or birds. Conclusions Passerine birds are a well-documented reservoir for S. Typhimurium in the Nordic region, often leading to transmission to both cats and humans. This outbreak highlights the role of animal exposure in the spread of S. Typhimurium and emphasize the need for timely, targeted public health communication on infection prevention measures.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

High-throughput fingerprinting of hydrolysable tannins in wine and oak wood using in-source fragmentation on QTOF and QQQ platforms - Yanxin Lin; Bruce S. Pan; Robert (Qiang) Sui; Ping Yu; Misha T. Kwasniewski (Food Chemistry, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Beyond the check-up: how well-child exams, pediatric specialists, and provider recommendations can close HPV vaccine gaps for Chinese American Teens - Lin Zhu; Xinrui Li; Elaine Zhiqing Liu; Philip T. Siu; Shumenghui Zhai; Chun Pan; Nikki Cao; Grace X. Ma (Cancer Causes & Control, 2026)
Purpose This study aimed to identify provider- and practice-level factors influencing human papillomavirus (HPV) vaccine uptake among Chinese American (CA) adolescents. Despite increasing public health efforts, HPV vaccination rates in this population remain suboptimal, and knowledge on the link between provider/practice characteristics and vaccine uptake is limited. Methods We analyzed data from 1,272 CA adolescents (aged 13–17) using the National Immunization Survey-Teen (2015–2019) datasets. Key measures included HPV vaccine initiation and completion (based on proxy reporting and verification), accompanied by various multilevel factors: provider-level (recommendation, specialty), practice-level (facility type, vaccine acquisition, well-child exam), parent-level (mother’s education, marital status), and adolescent-level characteristics. Weighted descriptive statistics and stepwise multivariate logistic regression were used to examine associations. Results Overall, 71.22% of CA adolescents initiated at least one HPV vaccine dose, while 48.14% completed the regimen. Provider's recommendation (initiation OR = 21.50, completion OR = 8.12), having a pediatrician (initiation OR = 5.37, completion OR = 3.20), and receiving the 11–12-year-old well-child exams significantly predict both initiation and completion. Regional disparities were observed, with adolescents in the Northeast and West showing higher completion rates than those in the South. Unexpectedly, adolescents not enrolled in school and those with mothers who had less than 12 years of education or were unmarried showed higher completion rates. Conclusion Provider recommendations and pediatric care are crucial for improving HPV vaccination rates among CA adolescents. Addressing regional disparities and implementing targeted interventions, including enhanced provider training focused on culturally sensitive communication, are essential to dismantle systemic barriers and improve comprehensive vaccination coverage in this underserved population.

Identification of antihypertensive peptides from Eudrilus eugeniae (Kinberg, 1867): in vitro ACE-I inhibition and peptide profiling - Roi Martin B. Pajimna; Omar A. Villalobos; Stephen B. Lirio; Hsi-Ya Huang; Chia-Her Lin; Allan Patrick Macabeo; Mary-Jho Anne T. Corpuz; Oliver B. Villaflores (Natural Product Research, 2026)

Impact of restoration on reducing carbon emissions from different blue carbon ecosystems - Siqi Nie; Xiaoguang Ouyang; Jia Lin; Fen Guo; Damien T. Maher; Zhaoliang Song; Zhifeng Yang (Ocean & Coastal Management, 2026)

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

Catalytic membrane reactors for H2 production and CO2 conversion: Advanced membranes and processes - Kai Chen; Leiqing Hu; Mark T. Swihart; Carl R.F. Lund; Haiqing Lin (Chemical Engineering Journal, 2026)

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A new externally coupled, physically-based multi-model framework for simulating subsurface and overland flow hydrological processes on hillslopes - A T M Sakiur Rahman; Jiří Šimůnek; Scott A. Bradford; Hoori Ajami; Menberu B. Meles; Lin Chen; Adam Szymkiewicz; Mateusz Pawlowicz; Juan S. Acero Triana; Alberto Casillas-Trasvina; Sahila Beegum (Journal of Hydrology, 2025)

The influence of in-car air quality on drivers’ brain states with hybrid fNIRS and EEG - Chao Wang; Yuanyuan Gao; Xiaojun Cheng; Xiaosu Hu; Erin T. Solovey; Yingzi Lin; Shichao Liu (Building and Environment, 2025)

A major and stable QTL confers impatiens necrotic spot virus resistance in lettuce cv. Eruption - Santosh Nayak; Kelley L. Richardson; Renée L. Eriksen; Daniel K. Hasegawa; William M. Wintermantel; Manoj Sapkota; Xuemei Tang; Shufen Chen; Meng Lin; Dongyan Zhao; Craig T. Beil; Moira J. Sheehan; et al. (Theoretical and Applied Genetics, 2025)
Key message A large effect and environmentally stable QTL was identified on LG2 that confers high levels of INSV resistance in lettuce cultivar Eruption. Abstract Impatiens necrotic spot virus (INSV) has recently emerged as a major threat to lettuce production in the Salinas Valley of California, the region which contributes over 60% of the US national supply. This thrips-transmitted virus can infect lettuce plants at any growth stage, causing premature death or a total loss of marketability. Both INSV and its thrips vector have broad host ranges, which complicate disease management. Utilizing genetic resistance is the most sustainable approach; however, complete immunity has not been identified and the genetic basis of resistance to INSV in lettuce remains poorly understood. This study aimed to identify quantitative trait loci (QTL) and elucidate the underlying mechanism of INSV resistance in ‘Eruption,’ a lettuce cultivar exhibiting highly stable partial resistance across environments. Using 162 F 6:8 recombinant inbred lines (RILs) developed from a cross between moderately susceptible ‘Reine des Glaces’ and ‘Eruption,’ and a genetic linkage map comprising 1598 single nucleotide polymorphism (SNP) markers, phenotypic data collected from field and greenhouse experiments consistently revealed a highly significant, major QTL on linkage group 2. This QTL exhibited partial dominance with additive effects, explaining up to 61% of the total phenotypic variation for INSV disease severity. Furthermore, INSV resistance was found to be highly heritable, with heritability estimates of up to 0.89, indicating strong genetic control. Results of this study are crucial for fine mapping and the development of marker-assisted selection assays to accelerate the breeding of more advanced INSV-resistant lettuce cultivars.

Genetic mapping of novel QTL for seed protein stability in food-grade soybean (Glycine max) - Andrew A. Mitchell; Feng Lin; Heng Ye; Tri Vuong; Zixiang Wen; Biructawit Tessema; Randall Laurenz; Raju Thada Magar; Henry T. Nguyen; Dechun Wang (Theoretical and Applied Genetics, 2025)
Key message Two novel quantitative trait loci associated with soybean protein content stability were identified on chromosomes 10 and 18. Haplotype analysis showed these to significantly improve stability without protein content penalty. Abstract Soybean seed protein content is a complex physiological trait under polygenic control and significant genotype by environment interaction. Protein content is largely influenced by ambient atmospheric temperature at pod-filling, with increased temperatures enhancing seed protein accumulation. The identification of genomic regions associated with protein content stability will facilitate an increased understanding of seed development physiology and assist in the development of more broadly adapted food-grade soybean cultivars. In this work, 210 recombinant inbred lines were derived from the intraspecific cross of the high protein accession BARC - 6 (PI 555396), and the low protein MSU breeding accession E14077 for the investigation of quantitative trait loci associated with protein content and protein content stability across multiple years and test locations. Indices for static protein content stability were used to estimate genome by environment interactions across Northern and Southern soybean production regions. Composite interval mapping returned one stable major effect QTL associated with protein content on chromosome 20 explaining approximately 20.7% of phenotypic variation. Two novel QTLs associated with absolute protein stability were detected on chromosomes 10 and 18, explaining approximately 8.6% and 7.6% of phenotypic variation, respectively. SNP-based haplotype analysis showed simultaneous favorable effects on protein content and stability when desirable alleles for these QTL were pyramided. These results will serve as a valuable tool for the molecular breeding of food-grade soybean cultivars harboring elevated protein content coupled with improved stability across varied environments, thus addressing a key challenge in meeting the global rise in soybean protein demand for both livestock feed and human consumption.

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Influence of Pearl river plume and coastal upwelling on planktonic foraminiferal assemblages in the northern South China Sea - Rick J. Yang; Hui-Ling Lin; Tai-Chun Lin; Jay Lee; James T. Liu; Horng-Sheng Mii (Marine Environmental Research, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Effect of soil properties on microcystin mobility and bioavailability in land-applied drinking water treatment residuals - Ying-Ren Lai; Zhian Lin; David Tomashefski; Elizabeth A. Dayton; Shane W. Whitacre; Jiyoung Lee; Nicholas T. Basta (Science of The Total Environment, 2025)

Segmentation of the Manila subduction zone and slab tearing beneath the Philippine mobile belt - Shu-Kun Hsu; Wen-Nan Wu; Lien-Kai Lin; Shiou-Ya Wang; Yi-Ching Yeh; Leo T. Armada; Carla B. Dimalanta; Kuan-Ting Chen; Yun-Jie Tsai; Ching-Hui Tsai (Journal of Asian Earth Sciences, 2025)

Non-extractant recycling of Ti, Fe, Ca and Al as value-added anatase, hematite, gypsum and nordstrandite from waste red mud - T. Su; S. Li; R. Bian; Y. Lin; S. Zhu (International Journal of Environmental Science and Technology, 2025)

Tapping the urban forest: Integrating tree canopy runoff (stemflow) into blue-green infrastructure - Jalayna Antoine; Meimei Lin; Alia M. El-Kulak; John T. Van Stan (Urban Forestry & Urban Greening, 2025)

P22-09 Toxicological Profiling of ZnO Nanoparticles: A Genotoxicity Mechanistic Study Using Alternative Test Methods - R.J. Chen; O. Lautan; S.-N. Chen; T.-Y. Lin; R. Pranata (Toxicology Letters, 2025)

Five novel RNA viruses of the invasive big-headed ant (Pheidole megacephala) - Charly T. Hartle; Chih-Chi Lee; Hung-Wei Hsu; Chun-Yi Lin; Kuan-Ling Liu; Joey Yin-Xin Chang; John A. Lawrence; Jia-Wei Tay; Chin-Cheng Scotty Yang (Archives of Virology, 2025)
The African big-headed ant, Pheidole megacephala , is one of the most destructive invasive ant species, posing a significant threat to native biodiversity and ecosystem function, particularly in island ecosystems. Despite recent efforts to characterize pathogens in other major invasive ants, P . megacephala has received comparatively little attention. In this study, we characterized five novel RNA viruses actively replicating in P . megacephala , which we have named Pheidole megacephala virus 1–5 (PmV1-5), and examined viral diversity and prevalence in two invasive populations in Taiwan and Hawaii. This ant possesses a unique trait of true morphological worker dimorphism (major and minor), allowing us to test whether virus prevalence differs between the major and minor worker castes. Our findings indicate that all five novel viruses were present in both populations, but viral prevalence was higher in Hawaii than in Taiwan, potentially due to differences in supercolony structure. Multiple-virus infections were common, with coinfection by PmV1 and PmV5 being the most frequent. Notably, we found no significant difference in infection patterns between major and minor workers, suggesting that virus distribution is stable within colonies and that sampling different castes does not introduce bias in pathogen detection. This study represents the first characterization of viral pathogens in P . megacephala and may contribute to the development of microbial control strategies against this globally invasive ant.

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Rankings of tuberculosis antibiotic treatment regimens are sensitive to spatial scale, detection limit, and initial host bacterial burden - Christian T. Michael; Maral Budak; Pauline Maiello; Kara Kracinovsky; Mark Rodgers; Jaime Tomko; Philana Ling Lin; JoAnne Flynn; Jennifer J. Linderman; Denise Kirschner (Journal of Theoretical Biology, 2025)

Synergistically combining peracetic acid and reduced graphene oxide membranes to degrade trace organic contaminants - Erda Deng; Zachary T. Kralles; Siavash Mohamadi; Sagnik Das; Ruveen Dias; Ning Dai; Haiqing Lin (Chemical Engineering Journal, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Quantifying the impact of climate and management strategies on groundwater conservation in the High Plains Aquifer - Zaichen Xiang; Ryan T. Bailey; Zachary T. Zambreski; Isaya Kisekka; Xiaomao Lin (Science of The Total Environment, 2025)

Uplift, tilting, and underlying structures of coastal northwestern Luzon, Philippines, deduced from marine terraces - Yiran Wang; Aron J. Meltzner; Jennifer Quye-Sawyer; Huili Yang; Yichen Pu; Jintang Qin; Lin Thu Aung; Zihan Aw; Andrea Denise A. Pamintuan; Noelynna T. Ramos (Quaternary Science Reviews, 2025)

Rethinking electrification strategy for China's passenger vehicle fleet decarbonization in resource-constrained environments - Xingyu Xue; Yin Li; Guorui Jia; Frank T. Hong; Zhenhong Lin; Chen Liu (Resources, Conservation and Recycling, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Operant social seeking to a novel peer after social isolation is associated with activation of nucleus accumbens shell in rats - Adedayo Olaniran; Kristine T. Garcia; Megan A. M. Burke; Hongyu Lin; Marco Venniro; Xuan Li (Psychopharmacology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Impact of phosphorus on the functional properties of extracellular polymeric substances recovered from sludge - Nouran T. Bahgat; Philipp Wilfert; Stephen J. Picken; Leo Sorin; Yuemei Lin; Leon Korving; Mark C.M. van Loosdrecht (Water Research, 2025)

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Landsat 8 OLI atmospheric correction neural network for inland waters in tropical regions - M. Van Nguyen; O. T. La; H. T. T. Nguyen; D. Heriza; B.-Y. Lin; G. Y. I. Ryadi; Chao-Hung Lin; Vinh Quang Pham (International Journal of Environmental Science and Technology, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

The Influence of Heterogeneous Processes on the Physicochemical Properties of Atmospheric Aerosols - Maofa Ge; Shengrui Tong; Lin Du; Lingyan Wu; Ting Lei; Kun Li; Minglan Xu; Narcisse T. Tsona; Wenqian Zhang; Hailiang Zhang (Advances in Atmospheric Sciences, 2025)
With the rapid development of the world economy, complex air pollution has increasingly become a serious threat; for example, with haze events occurring frequently in various regions of the globe. Recent evidence has indicated that secondary aerosols play an important role in haze formation, and that heterogeneous processes are among the main forces driving their explosive growth. In this regard, this paper reviews recent advances in the understanding of the impact of heterogeneous processes on haze chemistry, including the impact on NO 2 chemistry, marine aerosols, and the hygroscopicity and optical properties of atmospheric aerosols. It is distinguished from past reviews on this topic by focusing mainly on new insights from the past five years. We summarize the main findings of the impacts of heterogeneous processes on NO 2 chemistry, marine aerosols, and the physicochemical properties of atmospheric aerosols, and propose several future research directions.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

QTL mapping and whole-genome sequencing analysis for novel genetic resources associated with sucrose content in soybean [Glycine max (L.) Merr.] - Dongho Lee; Tri D. Vuong; James G. Shannon; Qijian Song; Feng Lin; Henry T. Nguyen (Theoretical and Applied Genetics, 2025)
Key message A major QTL for sucrose content was mapped on chromosome 8 in PI 506593. The novel genetic variants and candidate genes were further identified within the major QTL. Abstract Sucrose in soybean [ Glycine max (L.) Merr.] contribute to animal feed efficiency and natural sweetness of soy products. Thus, identifying novel genetic resources, such as quantitative trait loci (QTL), associated with sucrose content in soybean is essential for enhancing seed values. In this study, two recombinant inbred line populations derived from the same high sucrose donor parent, PI 506593, were used to identify significant QTLs. A total of 11 sucrose-related regions on chromosomes (Chrs.) 4, 5, 6, 8, 10, and 13 were identified using QTL analysis. Among them, four QTLs ( qSUC_08.1 , qSUC_08.2 , qSUC_08.3 , and qSUC_08.4 ) were clustered in the interval of 40,597,410–42,861,364 bp on Chr. 8, which was considered major QTL region. A desirable marker at 41,834,095 bp was tested in two populations, showing that two phenotypically extreme groups were efficiently differentiated. We further identified 44 and 54 candidate genes with non-synonymous mutations in the major QTL region based on the annotations of Wm82.a2.v1 and Wm82.a5.v1 assemblies, respectively. Among 54 candidate genes from Wm82.a5.v1, Protein Variation Effect Analyzer (PROVEAN) revealed that 18 genes contained 34 variants that had deleterious impacts on biological functions. RNA-seq analysis highlighted five candidate genes that were highly expressed in pod and seed tissues during reproductive stages and other plant parts. A gene, Gm_Wm82_23219 ( Glyma.08G293800 , Wm82.a2.v1) encoding proline-rich protein 4-like, was highlighted in both PROVEAN and RNA-seq analyses. Novel findings in this study will be valuable genetic resources in soybean breeding programs that aim to improve efficiency in animal feed and human food.

Efficient activation of UV-driven ozonation using ultrasonics for LDPE decomposition - A. Pattanateeradetch; C. Sakulthaew; Y.-T. Lin; A. Watcharenwong; A. Žgajnar Gotvajn; Y.-C. Chen; Q. Xu; C. Chokejaroenrat (Journal of Water Process Engineering, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Comprehensive evaluation of air quality: incense burning and night market emissions in Kaohsiung, Taiwan, using the ISCST3 air quality model - Pei-Cheng Cheng; Kassian T. T. Amesho; Yin-Cheng Huang; Yuan-Chung Lin; Feng-Chih Chou; Tsu-Nai Wang; Pei-Shih Chen; Kang-Shin Chen; Ken-Lin Chang; Chien-Hung Lee (Air Quality, Atmosphere & Health, 2025)

Toxicity risk from hip implant CoCrMo particles: The impact of dynamic flow rate on neuronal cells in microfluidic systems - Matthew Jeffers; Hemalatha Kanniyappan; Kai Yuan Cheng; Saundarya Prithweeraj; Govindaraj Perumal; Mark Barba; Yang Lin; Mathew T. Mathew (Toxicology Letters, 2024)

Temperature and carotid intima-medial thickness: The coronary artery risk development in young adults (CARDIA) study - Brian T. Joyce; Jie Yao; Yinan Zheng; Tao Gao; Drew Nannini; Shao Lin; Xin Li; Jaymie Meliker; Qianqian Song; David R. Jacobs; Donald Lloyd-Jones; Lifang Hou; et al. (Science of The Total Environment, 2024)

Analysis of contaminant residues in honey bee hive matrices - Donna A. Glinski; S. Thomas Purucker; Jeffrey M. Minucci; Rodney T. Richardson; Chia-Hua Lin; Reed M. Johnson; W. Matthew Henderson (Science of The Total Environment, 2024)

Structure and transport properties of FeS at planetary core conditions - E. Edmund; T. Bi; Z.M. Geballe; K. Brugman; J.-F. Lin; S. Chariton; V.B. Prakapenka; J. Minár; R.E. Cohen; A.F. Goncharov (Earth and Planetary Science Letters, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Using local ecological knowledge to inform regional conservation prioritization for threatened marine megafauna - Mingli Lin; Mingming Liu; Heidi Ma; Samuel T. Turvey; Songhai Li (Ocean & Coastal Management, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A review on the characterization of microwave-induced biowaste-derived activated carbons for dye adsorption - T. Kopac; S. D. Lin (International Journal of Environmental Science and Technology, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

An in vitro-in silico workflow for predicting renal clearance of PFAS - Hsing-Chieh Lin; Courtney Sakolish; Haley L. Moyer; Paul L. Carmichael; Maria T. Baltazar; Stephen S. Ferguson; Jason P. Stanko; Philip Hewitt; Ivan Rusyn; Weihsueh A. Chiu (Toxicology and Applied Pharmacology, 2024)

Response to “Overestimated bycatch owing to underestimated sampling bias” - Mingli Lin; Samuel T. Turvey; Songhai Li (Biological Conservation, 2024)

Fungal composition associated with host tree identity mediates nutrient addition effects on wood microbial respiration - Zhenhong Hu; Marcos Fernández‐Martínez; Qinsi He; Zhiyuan Xu; Lin Jiang; Guiyao Zhou; Ji Chen; Ming Nie; Qiang Yu; Hao Feng; Zhiqun Huang; Sean T. Michaletz (Ecology, 2024)
Fungi are key decomposers of deadwood, but the impact of anthropogenic changes in nutrients and temperature on fungal community and its consequences for wood microbial respiration are not well understood. Here, we examined how nitrogen and phosphorus additions (field experiment) and warming (laboratory experiment) together influence fungal composition and microbial respiration from decomposing wood of angiosperms and gymnosperms in a subtropical forest. Nutrient additions significantly increased wood microbial respiration via fungal composition, but effects varied with nutrient types and taxonomic groups. Specifically, phosphorus addition significantly increased wood microbial respiration (65%) through decreased acid phosphatase activity and increased abundance of fast‐decaying fungi (e.g., white rot), while nitrogen addition marginally increased it (30%). Phosphorus addition caused a greater increase in microbial respiration in gymnosperms than in angiosperms (83.3% vs. 46.9%), which was associated with an increase in Basidiomycota:Ascomycota operational taxonomic unit abundance in gymnosperms but a decrease in angiosperms. The temperature dependencies of microbial respiration were remarkably constant across nutrient levels, consistent with metabolic scaling theory hypotheses. This is because there was no significant interaction between temperature and wood phosphorus availability or fungal composition, or the interaction among the three factors. Our results highlight the key role of tree identity in regulating nutrient response of wood microbial respiration through controlling fungal composition. Given that the range of angiosperm species may expand under climate warming and forest management, our data suggest that expansion will decrease nutrient effects on forest carbon cycling in forests previously dominated by gymnosperm species.

Assessing the suitability of leachability-based screening levels for per- and polyfluoroalkyl substances (PFAS) risk assessment - Jake T. Thompson; Dreyton J. Lott; Ashley M. Lin; John A. Bowden; Leah Stuchal; Timothy G. Townsend (Science of The Total Environment, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Non-targeted analysis and toxicity prediction for evaluation of photocatalytic membrane distillation removing organic contaminants from hypersaline oil and gas field-produced water - Himali M.K. Delanka-Pedige; Robert B. Young; Maha T. Abutokaikah; Lin Chen; Huiyao Wang; Kanchana A.B.I. Imihamillage; Sean Thimons; Michael A. Jahne; Antony J. Williams; Yanyan Zhang; Pei Xu (Journal of Hazardous Materials, 2024)

Experimental and theoretical constraints on lithium isotope fractionation during brine evaporation and halite precipitation - Yongjie Lin; Marcello Merli; Paolo Censi; Simon A.T. Redfern; Yue Zhao; Qing-Zhu Yin; Mianping Zheng; Xudong Yu; Yongsheng Zhang; William J. Knapp; Edward T. Tipper (Geochimica et Cosmochimica Acta, 2024)

Marine macro-litter sources and ecological impact: a review - Van-Giang Le; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Nguyen T. Quang Hung; Akhil P. Khedulkar; Nguyen K. Hue; Phung T. Thu Trang; Arvind Kumar Mungray; D. Duc Nguyen (Environmental Chemistry Letters, 2024)

Sight and blindness: The relationship between ostracod eyes, water depth, and light availability in the Arctic Ocean - Jingwen Zhang; Moriaki Yasuhara; Chih‐Lin Wei; Skye Yunshu Tian; Kyawt K. T. Aye; Laura Gemery; Thomas M. Cronin; Peter Frenzel; David J. Horne (Limnology and Oceanography, 2024)
Eye loss has been a long‐standing interest in evolutionary biology. Many organisms that inhabit environments without light penetration, for example the deep sea, exhibit eye loss and thus become blind. However, water‐depth distribution of eyes in marine organisms is poorly understood. Ostracods are widely distributed crustaceans, and many sighted marine ostracods have eye tubercles (lenses) on their shells. Since eye tubercles are visible on the shells illustrated in much literature, it is easy to determine their presence or absence via a literature survey. Here, we used a large Arctic‐wide ostracod census dataset (Arctic Ostracode Database) to calculate the eye index (the percentage of species with eyes), and compare them with water depth and light availability. As water depth increases, eye index values decrease and become constantly zero in water deeper than 1000 m. Similar decline of sighted species with increasing depth is also known in isopods and amphipods, suggesting that it may be common in other crustaceans and perhaps in deep‐sea organisms in general. We also show that eye index values increase as light availability increases. This study is the first to quantify how distributions of sighted and blind species change with light availability, giving baseline information on vision in the deep sea.

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

How turtles keep their cool: Seasonal and diel basking patterns in a tropical turtle - Rosie Kidman; Donald T. McKnight; Lin Schwarzkopf; Eric J. Nordberg (Journal of Thermal Biology, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Compressive behavior of FRP-confined normal concrete or seawater sea-sand concrete containing FRP-bar recycled coarse aggregates - Z.Y. Gao; S.S. Zhang; Guan Lin; T. Yu; X.F. Nie (Engineering Structures, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Insights on volatile metals in landfill gas as determined from advanced treatment media - Thomas J. Smallwood; Jordan K. Magnuson; Jake T. Thompson; Ashley M. Lin; Timothy G. Townsend (Journal of Hazardous Materials, 2024)

Few-cycle atomic layer deposition to nanoengineer polybenzimidazole for H2/CO2 separation - Leiqing Hu; Won-Il Lee; Ashwanth Subramanian; Erda Deng; Kim Kisslinger; Shouhong Fan; Vinh T. Bui; Yifu Ding; Chang-Yong Nam; Haiqing Lin (Chemical Engineering Journal, 2024)

Multi-scale numerical simulations of the synoptic environment, Diablo windstorm, and wildfire formation mechanisms for the Tubbs Fire (2017) - Jackson T. Wiles; Yuh-Lang Lin; Michael L. Kaplan (Meteorology and Atmospheric Physics, 2024)

Sexual orientation and gender identity inequities in cervical cancer screening by race and ethnicity - Emmeline Lin; Patrycja Sleboda; Bobbie J. Rimel; Jarvis T. Chen; Diana V. Hernandez; Geetanjali D. Datta (Cancer Causes & Control, 2024)
Background In the United States, inequities in preventive health behaviors such as cervical cancer screening have been documented. Sexual orientation, gender identity, and race/ethnicity all individually contribute to such disparities. However, little work has investigated their joint impact on screening behavior. Methods Using sampling weighted data from the 2016 and 2018 Behavioral Risk Factor Surveillance System, we assessed differences in two metrics via chi-square statistics: 1) lifetime uptake, and 2) up-to-date cervical cancer screening by sexual orientation and gender identity, within and across racial/ethnic classifications. Results Within all races, individuals who identify as members of sexual and gender minority (SGM) communities reported higher rates of never being screened (except for Black transgender men) than straight or cisgender individuals ( p < 0.0001). [ *START* Across all races, the Asian/Pacific Islander transgender population (32.4%; weighted n ( w.n. ) = 1,313) had the lowest proportion of lifetime screening, followed by the Asian/Pacific Islander gay/lesbian (53.0%, w.n. = 21,771), Hispanic transgender (58.7%; w.n. = 24,780), Asian/Pacific Islander bisexual (61.8%, w.n. = 54,524), and Hispanic gay/lesbian (69.6%, w.n. = 125,781) populations. *END* ] Straight or cisgender Non-Hispanic White ( w.n. = 40,664,476) individuals had the highest proportion of lifetime screening (97.7% and 97.5%, respectively). However, among individuals who had been screened at least once in their lifetime, identifying as SGM was not associated with a decreased proportion of up-to-date screening within or between races. Conclusions Due to small sample sizes, especially among Asian/Pacific Islander and Hispanic populations, confidence intervals were wide. Heterogeneity in screening participation by SGM status within and across racial/ethnic groups were observed. Impact These screening disparities reveal the need to disaggregate data to account for intersecting identities and for studies with larger sample sizes to increase estimate reliability.

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

A shared role of the myocardin-family transcriptional coactivators in cardiomyocyte maturation - Yuxuan Guo; Yangpo Cao; Blake D. Jardin; Neil Mazumdar; Congting Guo; Luzi Yang; Junsen Lin; Zhan Chen; Qing Ma; Mingming Zhao; Erdan Dong; William T. Pu (Science China Life Sciences, 2023)

Establishment of a developmental atlas and transgenetic tools in the ascidian Styela clava - Boyan Lin; Wenjie Shi; Qiongxuan Lu; Takumi T. Shito; Haiyan Yu; Bo Dong (Marine Life Science & Technology, 2023)

Advancing co-production for transformative change by synthesizing guidance from case studies on the sustainable management and governance of natural resources - Fernanda A. van Maurik Matuk; Bas Verschuuren; Piero Morseletto; Torsten Krause; David Ludwig; Steven J. Cooke; Moacir Haverroth; Marieke Meesters; Thomas J.M. Mattijssen; Sabine Keßler; Tomaz R. Lanza; Esther Milberg; et al. (Environmental Science & Policy, 2023)

Significant catalyst savings and reaction kinetics enhancement for catalytic micro-combustors via non-uniform catalyst segmentation - Emily Lin; Chad T. Wilson; Arny Leroy; Sili Deng (Chemical Engineering Journal, 2023)

Are associations between obesity and prostate cancer outcomes following radical prostatectomy the same in smokers and non-smokers? Results from the SEARCH Cohort - Ivy T. Liu; Lin Gu; Amanda M. De Hoedt; Matthew R. Cooperberg; Christopher L. Amling; Christopher J. Kane; Zachary Klaassen; Martha K. Terris; Lourdes Guerrios-Rivera; Adriana C. Vidal; William J. Aronson; Stephen J. Freedland; et al. (Cancer Causes & Control, 2023)

Life History Parameters to Inform Pattern of Prenatal Investment in Marine Mammals - Xiaoyu Huang; Mingming Liu; Samuel T. Turvey; Mingli Lin; Songhai Li (Journal of Marine Science and Engineering, 2023)
Marine mammals are a diverse group of aquatic animals that exhibit wide variation in body size, living conditions, breeding habitat, social behaviour and phylogeny. Although case studies about prenatal investment in cetaceans and pinnipeds have been investigated, comparative studies across different marine mammal taxonomic groups have not yet been conducted systematically. Here, six life history parameters from 75 marine mammal species were collected based on a meta-analysis of the existing literature, and prenatal investment patterns for different taxonomic groups were explored using an unsupervised artificial neural network of a self-organizing map (SOM). Most marine mammal species can be clearly divided into two clusters of small-bodied taxa (small-bodied toothed whales, pinnipeds) and large-bodied taxa (baleen whales, sperm whales and beaked whales, large-bodied toothed whales) based on their distribution within SOM feature maps. Gestation periods and breeding intervals are significantly shorter in pinnipeds than in small-bodied toothed dolphins despite being similar in body size, indicating their adaption to birthing and nursing on land or ice floes. Specific deep-dive feeding behaviour seems to have no impact on the prenatal investment of beaked whales and sperm whales, as these species exhibit a similar capital breeding strategy to baleen whales. Medium-bodied sirenians adopt an intermediate strategy between small-bodied and large-bodied toothed whales, suggesting their prenatal investment strategy is not affected by herbivorous habits. Overall, our results support the body-size hypothesis and breeding-substrate hypothesis and indicate that prenatal investment strategies of marine mammals are possibly not influenced by feeding habits or social behaviour. We suggest that effective conservation measures for small-bodied toothed whales and pinnipeds should prioritize the protection of habitats and minimize human disturbance, whereas conservation measures for large-bodied whales and beaked whales should focus on strategies to prevent substantial declines in population size.

Improving biomethane production from biochar-supplemented two-stage anaerobic digestion of on-farm feedstocks - Xue Ning; Chen Deng; Daniel T. Hickey; Anga Hackula; Richard O'Shea; David M. Wall; Richen Lin; Jerry D. Murphy (Journal of Cleaner Production, 2023)

An interview-based investigation of marine megafauna bycatch in the northern South China Sea - Mingli Lin; Mingming Liu; Samuel T. Turvey; Songhai Li (Biological Conservation, 2023)

Parameterizations for sea spray aerosol production flux - Aijing Song; Jianlong Li; Narcisse T. Tsona; Lin Du (Applied Geochemistry, 2023)

BioDeepTime: A database of biodiversity time series for modern and fossil assemblages - Jansen Smith; Marina C. Rillo; Ádám T. Kocsis; Maria Dornelas; David Fastovich; Huai‐Hsuan M. Huang; Lukas Jonkers; Wolfgang Kiessling; Qijian Li; Lee Hsiang Liow; Miranda Margulis‐Ohnuma; Stephen Meyers; et al. (Global Ecology and Biogeography, 2023)
Motivation We have little understanding of how communities respond to varying magnitudes and rates of environmental perturbations across temporal scales. BioDeepTime harmonizes assemblage time series of presence and abundance data to help facilitate investigations of community dynamics across timescales and the response of communities to natural and anthropogenic stressors. BioDeepTime includes time series of terrestrial and aquatic assemblages of varying spatial and temporal grain and extent from the present‐day to millions of years ago. Main Types of Variables Included BioDeepTime currently contains 7,437,847 taxon records from 10,062 assemblage time series, each with a minimum of 10 time steps. Age constraints, sampling method, environment and taxonomic scope are provided for each time series. Spatial Location and Grain The database includes 8752 unique sampling locations from freshwater, marine and terrestrial ecosystems. Spatial grain represented by individual samples varies from quadrats on the order of several cm 2 to grid cells of ~100 km 2 . Time Period and Grain BioDeepTime in aggregate currently spans the last 451 million years, with the 10,062 modern and fossil assemblage time series ranging in extent from years to millions of years. The median extent of modern time series is 18.7 years and for fossil series is 54,872 years. Temporal grain, the time encompassed by individual samples, ranges from days to tens of thousands of years. Major Taxa and Level of Measurement The database contains information on 28,777 unique taxa with 4,769,789 records at the species level and another 271,218 records known to the genus level, including time series of benthic and planktonic foraminifera, coccolithophores, diatoms, ostracods, plants (pollen), radiolarians and other invertebrates and vertebrates. There are to date 7012 modern and 3050 fossil time series in BioDeepTime. Software Format SQLite, Comma‐separated values.

Enzymatically hydrolyzed fluorescence-based chemical probe enables in situ mapping of chitinase activity in the rhizosphere - Elias K. Zegeye; Vivian S. Lin; Jamie R. Nuñez; Nick A. Sconzo; Samuel O. Purvine; Aaron T. Wright; James J. Moran (Soil Biology and Biochemistry, 2023)

Mn-MOFs-derived Mn2O3 as an effective peroxymonosulfate activator for the degradation of organics in water - V. D. Thao; N. T. Dung; N. D. Duc; T. T. Trang; D. T. M. Thanh; N. T. Phuong; N. T. Thuy; K.-Y. A. Lin; N. N. Huy (International Journal of Environmental Science and Technology, 2023)

The impact of education level on residents’ carbon consumption in China - Y.-N. Lin; Y.-H. Chiu; T.-H. Chang; T.-Y. Lin; S.-Y. Chiu (International Journal of Environmental Science and Technology, 2023)

A review of hydrogen production optimization from the reforming of C1 and C2 alcohols via artificial neural networks - Wei-Hsin Chen; Partha Pratim Biswas; Aristotle T. Ubando; Eilhann E. Kwon; Kun-Yi Andrew Lin; Hwai Chyuan Ong (Fuel, 2023)

A systematic review from basics to omics on bacteriophage applications in poultry production and processing - Md. Rashedul Islam; Carlos E. Martinez-Soto; Janet T. Lin; Cezar M. Khursigara; Shai Barbut; Hany Anany (Critical Reviews in Food Science and Nutrition, 2023)

Feasibility of a TDR-based technique for fluid hydrocarbon leak detection - Chih-Ping Lin; Yin Jeh Ngui; Yi-Pei Chan; Albert T. Yeung (Process Safety and Environmental Protection, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Characteristics and correlation of soil low-molecular-weight organic acids and nutrients in four plantations in red soil area of south China - Y. M. Ren; Z. J. Hou; T. Su; Z. R. Lin; A. Q. Liu; L. P. Cai (International Journal of Environmental Science and Technology, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Economic and environmental feasibility of recycling flexible plastic packaging from single stream collection - Yingqian Lin; Michael H. Severson; Ruby T. Nguyen; Anne Johnson; Christopher King; Beth Coddington; Hongqiang Hu; Brennan Madden (Resources, Conservation and Recycling, 2023)

Effects of urbanisation on ecosystem service values: A case study of Nha Trang, Vietnam. - Kien T. Pham; Tang-Huang Lin (Land Use Policy, 2023)

The contrast in suspended particle dynamics at surface and near bottom on the river-dominated northern South China Sea shelf in summer: implication on physics and biogeochemistry coupling - Jay Lee; James T. Liu; Yu-Shih Lin; Chen-Tung Arthur Chen; Bo-Shian Wang (Frontiers in Marine Science, 2023)
To understand the process-response relations among physical forcing and biogeochemical properties of suspended particles (SPs) in the river-dominated northern South China Sea shelf, a 5-day shipboard observation was conducted at a fixed location on the dispersal pathway of the Zhujiang (Pearl) River plume (ZRP) in the summer of 2016. Instrumented moorings were deployed near the sampling site to record the flow and wave fields every 10 minutes. Hydrographic properties were measured hourly to identify different water masses. Water and SPs samples at the surface (3 m) and near the bottom (3 m above the bed) were taken every 3 h for the analyses of nutrients, chlorophyll-a (Chl-a), and particulate organic matter (POM including POC, PN, and δ 13 C POC ). Meanwhile, the grain-size composition of SPs and seafloor sediment were also analyzed. Results showed that monsoon winds drove cold upwelling and ZRP waters at the surface. Both the upwelling and ZRP regimes contained newly produced marine phytoplankton based on low POC/Chl-a ratio (PC ratio) and enriched δ 13 C POC. However, SPs in the ZRP regime were smaller (<153 µm), having denser particle bulk density, and less enriched δ 13 C POC , indicating different bio-communities from the upwelling regime. EOF analysis of the surface data suggested that mixing processes and the dispersal of the ZRP regime were mainly controlled by far-field storm winds, tidal modulation, and strength of mixing. On the other hand, a bottom nepheloid layer (BNL) was observed, mainly consisting of SPs<63 μm with higher bulk density than SPs at the surface. POM in the BNL was degraded and δ 13 C POC -depleted according to the PC ratio and δ 13 C POC . EOF analysis of the near-bottom data indicated that the dominant physical processes influencing the biogeochemical properties of SPs in the BNL were jointly the upwelling-associated lateral transport (first order) and tide-related resuspension (second order). Our study identified the contrast between the surface and near-bottom regimes with the coupling patterns among physical forcing and physiochemical properties of SPs using good constraints on particle dynamics and particle sources.

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Hydroclimate dynamics during the Plio-Pleistocene transition in the northwest Pacific realm - Romain Vaucher; Christian Zeeden; Amy I. Hsieh; Stefanie Kaboth-Bahr; Andrew T. Lin; Chorng-Shern Horng; Shahin E. Dashtgard (Global and Planetary Change, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

A chromosome-level genome assembly reveals that a bipartite gene cluster formed via an inverted duplication controls monoterpenoid biosynthesis in Schizonepeta tenuifolia - Chanchan Liu; Samuel J. Smit; Jingjie Dang; Peina Zhou; Grant T. Godden; Zheng Jiang; Wukun Liu; Licheng Liu; Wei Lin; Jinao Duan; Qinan Wu; Benjamin R. Lichman (Molecular Plant, 2023)

On the occurrence of low concentration hyperpycnal river plumes in a small mountainous river-canyon system - Sheng-De Tsai; Yu-Chi Lin; Andhy Romdani; Jia-Lin Chen; Ray T. Hsu; James T. Liu (Continental Shelf Research, 2023)

Deep eutectic solvents in the transformation of biomass into biofuels and fine chemicals: a review - Kassian T. T. Amesho; Yuan-Chung Lin; S. Venkata Mohan; Subham Halder; Vinoth Kumar Ponnusamy; Syu-Ruei Jhang (Environmental Chemistry Letters, 2023)

Dancing to a different tune: changing reproductive seasonality in an introduced chital deer population - Catherine L. Kelly; Lin Schwarzkopf; Iain J. Gordon; Anthony Pople; David L. Kelly; Ben T. Hirsch (Oecologia, 2022)
Male and female reproductive behaviour is typically synchronised. In species such as those in the family Cervidae , reproductive timing is often cued by photoperiod, although in females, it can be dependent on body condition. When a species is introduced to a novel environment, the environment changes, or responses of the sexes to such cues differ, asynchronous reproductive behaviour between males and females may occur. We investigated the seasonality of reproductive behaviour in introduced chital deer in northern Queensland by examining male antler phase in relation to female conception rates. We then analysed the influence of different variables likely to affect the timing of male and female reproductive physiology. The lowest percentage of chital in hard antler in any 1 month in this study was 35% (Fig. 1), but the average value was closer to 50%, thus there was a seasonal peak in antler phase linked with photoperiod. Females conceived at any time of year, but were strongly influenced by the amount of rainfall 3 months prior to conception. This resulted in varying conception peaks year-to-year that often did not correspond to the male’s peak in hard antler. In this system, a proportion of males and females were physiologically and behaviourally ready to mate at any time of the year. We predict that differences in the timing of the peaks between the males and females will lead to increased reproductive skew (variation in reproductive success among individual males). This pattern may select for different mating strategies or physiological mechanisms to increase reproductive success.

Correction to: Breeding for disease resistance in soybean: a global perspective - Feng Lin; Sushil Satish Chhapekar; Caio Canella Vieira; Marcos Paulo Da Silva; Alejandro Rojas; Dongho Lee; Nianxi Liu; Esteban Mariano Pardo; Yi-Chen Lee; Zhimin Dong; Jose Baldin Pinheiro; Leonardo Daniel Ploper; et al. (Theoretical and Applied Genetics, 2022)

Breeding for disease resistance in soybean: a global perspective - Feng Lin; Sushil Satish Chhapekar; Caio Canella Vieira; Marcos Paulo Da Silva; Alejandro Rojas; Dongho Lee; Nianxi Liu; Esteban Mariano Pardo; Yi-Chen Lee; Zhimin Dong; Jose Baldin Pinheiro; Leonardo Daniel Ploper; et al. (Theoretical and Applied Genetics, 2022)
Key message This review provides a comprehensive atlas of QTLs, genes, and alleles conferring resistance to 28 important diseases in all major soybean production regions in the world. Abstract Breeding disease-resistant soybean [ Glycine max (L.) Merr.] varieties is a common goal for soybean breeding programs to ensure the sustainability and growth of soybean production worldwide. However, due to global climate change, soybean breeders are facing strong challenges to defeat diseases. Marker-assisted selection and genomic selection have been demonstrated to be successful methods in quickly integrating vertical resistance or horizontal resistance into improved soybean varieties, where vertical resistance refers to R genes and major effect QTLs, and horizontal resistance is a combination of major and minor effect genes or QTLs. This review summarized more than 800 resistant loci/alleles and their tightly linked markers for 28 soybean diseases worldwide, caused by nematodes, oomycetes, fungi, bacteria, and viruses. The major breakthroughs in the discovery of disease resistance gene atlas of soybean were also emphasized which include: (1) identification and characterization of vertical resistance genes reside rhg1 and Rhg4 for soybean cyst nematode, and exploration of the underlying regulation mechanisms through copy number variation and (2) map-based cloning and characterization of Rps11 conferring resistance to 80% isolates of Phytophthora sojae across the USA. In this review, we also highlight the validated QTLs in overlapping genomic regions from at least two studies and applied a consistent naming nomenclature for these QTLs. Our review provides a comprehensive summary of important resistant genes/QTLs and can be used as a toolbox for soybean improvement. Finally, the summarized genetic knowledge sheds light on future directions of accelerated soybean breeding and translational genomics studies.

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Acanthopagrus oconnorae , a new species of seabream (Sparidae) from the Red Sea - Lucía Pombo‐Ayora; Viktor N. Peinemann; Collin T. Williams; Song He; Yu Jia Lin; Yukio Iwatsuki; Donal D. C. Bradley; Michael L. Berumen (Journal of Fish Biology, 2022)
A new species of sparid fish, Acanthopagrus oconnorae , is described based on 11 specimens collected in the shallow (0–1 m depth) mangrove‐adjacent sandflats of Thuwal, Saudi Arabia. The new species is distinguished from its congeners by the following combination of characters: second anal‐fin spine 12.8%–16.6% of standard length (SL); 3½ scale rows between the fifth dorsal‐fin spine and lateral line; suborbital width 5.7%–6.7% of SL; eyes positioned at the anterior edge of the head, often forming a weakly convex break in an otherwise gently curved head profile, when viewed laterally; caudal fin light yellow with black posterior margin (approximately half of fin); anal fin dusky grey, with posterior one‐fifth of the fin light yellow; black streaks on inter‐radial membranes of anal fin absent. The most similar species to A. oconnorae is Acanthopagrus vagus , which differs by the presence of a w‐shaped anterior edge of the scaled predorsal area, a more acute snout and black streaks on the inter‐radial membranes of the anal fin. Phylogenetic placement and species delimitation of A. oconnorae are discussed based on COI, CytB and 16S sequences. It is hypothesized that ecology and behaviour explain how this species avoided detection despite its likely occurrence in coastal areas of the Red Sea with historically high fishing pressure.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Activation of Neuropeptide Y2 Receptor Can Inhibit Global Cerebral Ischemia-Induced Brain Injury - Reggie Hui-Chao Lee; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Alexandre Couto e Silva; Harlee E. Possoit; Garrett A. Clemons; Christina H. Acosta; Victoria A. de la Llama; Jake T. Neumann; Hung Wen Lin (NeuroMolecular Medicine, 2022)

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

Evolution of Bordetella pertussis in the acellular vaccine era in Norway, 1996 to 2019 - Lin T. Brandal; Didrik F. Vestrheim; Torbjørn Bruvik; Ragnhild B. Roness; Martha L. Bjørnstad; Margrethe Greve-Isdahl; Anneke Steens; Ola B. Brynildsrud (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
We described the population structure of Bordetella pertussis ( B. pertussis ) in Norway from 1996 to 2019 and determined if there were evolutionary shifts and whether these correlated with changes in the childhood immunization program. We selected 180 B. pertussis isolates, 22 from the whole cell vaccine (WCV) era (1996–1997) and 158 from the acellular vaccine (ACV) era (1998–2019). We conducted whole genome sequencing and determined the distribution and frequency of allelic variants and temporal changes of ACV genes. Norwegian B. pertussis isolates were evenly distributed across a phylogenetic tree that included global strains. We identified seven different allelic profiles of ACV genes (A–F), in which profiles A1, A2, and B dominated (89%), all having pertussis toxin ( ptxA ) allele 1, pertussis toxin promoter ( ptxP ) allele 3, and pertactin ( prn ) allele 2 present. Isolates with ptxP1 and prn1 were not detected after 2007, whereas the prn2 allele likely emerged prior to 1972, and ptxP3 before the early 1980s. Allele conversions of ACV genes all occurred prior to the introduction of ACV. Sixteen percent of our isolates showed mutations within the prn gene. ACV and its booster doses (implemented for children in 2007 and adolescents in 2013) might have contributed to evolvement of a more uniform B. pertussis population, with recent circulating strains having ptxA1 , ptxP3 , and prn2 present, and an increasing number of prn mutations. These strains clearly deviate from ACV strains ( ptxA1 , ptxP1 , prn1 ), and this could have implications for vaccine efficiency and, therefore, prevention and control of pertussis.

Present-Day PM2.5 over Asia: Simulation and Uncertainty in CMIP6 ESMs - Xiaole Su; Tongwen Wu; Jie Zhang; Yong Zhang; Junli Jin; Qing Zhou; Fang Zhang; Yiming Liu; Yumeng Zhou; Lin Zhang; Steven T. Turnock; Kalli Furtado (Journal of Meteorological Research, 2022)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Special Issue: Geostatistics and Machine Learning - Sandra De Iaco; Dionissios T. Hristopulos; Guang Lin (Mathematical Geosciences, 2022)
Recent years have seen a steady growth in the number of papers that apply machine learning methods to problems in the earth sciences. Although they have different origins, machine learning and geostatistics share concepts and methods. For example, the kriging formalism can be cast in the machine learning framework of Gaussian process regression. Machine learning, with its focus on algorithms and ability to seek, identify, and exploit hidden structures in big data sets, is providing new tools for exploration and prediction in the earth sciences. Geostatistics, on the other hand, offers interpretable models of spatial (and spatiotemporal) dependence. This special issue on Geostatistics and Machine Learning aims to investigate applications of machine learning methods as well as hybrid approaches combining machine learning and geostatistics which advance our understanding and predictive ability of spatial processes.

An extended Human Connectome Project multimodal parcellation atlas of the human cortex and subcortical areas - Chu-Chung Huang; Edmund T. Rolls; Jianfeng Feng; Ching-Po Lin (Brain Structure and Function, 2022)

Diversity and Zonation of Benthic Amphipod Crustaceans Affected by the Mississippi Submarine Canyon in the Northern Gulf of Mexico - Yousria S. Soliman; Gilbert T. Rowe; Mary Wicksten; Chih-Lin Wei (Frontiers in Marine Science, 2022)
Amphipod crustacean diversity and zonation are described from the large Mississippi Canyon that extends from the continental shelf across the entire continental margin. Benthic amphipods were sampled on four cruises from 2000 to 2004 from six locations in the Mississippi Canyon from depths of 480 through 2,750 m, and compared with five locations in a second transect on the open continental slope approximately 100 km west of the canyon to assess the canyon effect on the structure and composition of amphipod assemblages. Five replicates were collected from each location using 0.2 m –2 GOMEX box corer. Amphipods amounted to 40% of the total faunal abundance within the canyon compared to only 4% in the non-canyon samples. Of the seventy-two species (19 families) collected, 61 were encountered in the canyon compared to 38 on the non-canyon transect. The trough-like head of the canyon (480 m) supported high densities (4,446–26,933 ind./m 2 ) of the filter feeding, tube dwelling ampeliscid amphipod ( Ampelisca mississippiana ), the highest densities sampled compared to any other single species, at any other location, either within or outside the canyon, reflecting extreme flux of organic detritus from the continental shelf. The dominance by this single species suppressed the within – habitat (alpha) diversity and evenness, compared to relatively high diversity within the 1,000–1,500 m depths interval both in and outside the canyon. The species richness and alpha diversity exhibited mid-depth maxima at ca. 1,100 m both in and out of the canyon. High species richness (61) over the entire length of the canyon is presumed to be a function of greater topographic complexity and intermittent mass wasting of sediment down the canyon axis. The absence of nestedness is attributed to the amphipod reproductive pattern that lacks dispersive larval stages and brooding comparatively small numbers of eggs in this taxon. Despite depressed diversity at the head of the canyon, the fact that the number of amphipod species in the Mississippi Canyon was 1.5 times their numbers on the adjacent slope suggests that this physiographic feature enriches geographic-scale species diversity.

Mycorrhizal and rhizobial interactions influence model grassland plant community structure and productivity - Jiqiong Zhou; Gail W. T. Wilson; Adam B. Cobb; Yingjun Zhang; Lin Liu; Xinquan Zhang; Feida Sun (Mycorrhiza, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Conservation planning on China's borders with Myanmar, Laos, and Vietnam - Lin Wang; Bin Yang; Yang Bai; Xiaoqiang Lu; Richard T. Corlett; Yunhong Tan; Xiao‐Yong Chen; Jianguo Zhu; Yan Liu; Rui‐Chang Quan (Conservation Biology, 2021)
Transboundary conservation is playing an increasingly important role in maintaining ecosystem integrity and halting biodiversity loss caused by anthropogenic activities. However, lack of information on species distributions in transboundary regions and understanding of the threats in these areas impairs conservation. We developed a spatial conservation plan for the transboundary areas between Yunnan province, southwestern China, and neighboring Myanmar, Laos, and Vietnam in the Indo‐Burma biodiversity hotspot. To identify priority areas for conservation and restoration, we determined species distribution patterns and recent land‐use changes and examined the spatiotemporal dynamics of the connected natural forest, which supports most species. We assessed connectivity with equivalent connected area (ECA), which is the amount of reachable habitat for a species. An ECA incorporates the presence of habitat in a patch and the amount of habitat in other patches within dispersal distance. We analyzed 197,845 locality records from specimen collections and monographs for 21,004 plant and vertebrate species. The region of Yunnan immediately adjacent to the international borders had the highest species richness, with 61% of recorded species and 56% of threatened vertebrates, which suggests high conservation value. Satellite imagery showed the area of natural forest in the border zone declined by 5.2% (13,255 km 2 ) from 1995 to 2018 and monoculture plantations increased 92.4%, shrubland 10.1%, and other cropland 6.2%. The resulting decline in connected natural forest reduced the amount of habitat, especially for forest specialists with limited dispersal abilities. The most severe decline in connectivity was along the Sino‐Vietnamese border. Many priority areas straddle international boundaries, indicating demand and potential for establishing transboundary protected areas. Our results illustrate the importance of bi‐ and multilateral cooperation to protect biodiversity in this region and provide guidance for future conservation planning and practice.

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Phylogeography of Blue Corals (Genus Heliopora) Across the Indo-West Pacific - Hiroki Taninaka; Davide Maggioni; Davide Seveso; Danwei Huang; Abram Townsend; Zoe T. Richards; Sen-Lin Tang; Naohisa Wada; Taisei Kikuchi; Hideaki Yuasa; Megumi Kanai; Stéphane De Palmas; et al. (Frontiers in Marine Science, 2021)
Species delimitation of corals is one of the most challenging issues in coral reef ecology and conservation. Morphology can obscure evolutionary relationships, and molecular datasets are consistently revealing greater within-species diversity than currently understood. Most phylogenetic studies, however, have examined narrow geographic areas and phylogeographic expansion is required to obtain more robust interpretations of within- and among- species relationships. In the case of the blue coral Heliopora , there are currently two valid species ( H. coerulea and H. hiberniana ) as evidenced by integrated genetic and morphological analyses in northwestern Australia. There are also two distinct genetic lineages of H. coerulea in the Kuroshio Current region that are morphologically and reproductively different from each other. Sampling from all Heliopora spp. across the Indo-Pacific is essential to obtain a more complete picture of phylogeographic patterns. To examine phylogenetic relationships within the genus Heliopora , we applied Multiplexed inter simple sequence repeat (ISSR) Genotyping by sequencing (MIG-seq) on > 1287 colonies across the Indo-West Pacific. Maximum likelihood phylogenetic trees indicated the examined Heliopora samples comprise three genetically distinct groups: H. coerulea group, H. hiberniana group, and a new undescribed Heliopora sp. group with further subdivisions within each group. Geographic structuring is evident among the three species with H. hiberniana group found in the Indo-Malay Archipelago and biased toward the Indian Ocean whilst Heliopora sp. was only found in the Kuroshio Current region and Singapore, indicating that this taxon is distributed in the western Pacific and the Indo-Malay Archipelago. Heliopora coerulea has a wider distribution, being across the Indian Ocean and western Pacific. This study highlights the effectiveness of phylogenetic analysis using genome-wide markers and the importance of examining populations across their distribution range to understand localized genetic structure and speciation patterns of corals.

Distribution, Temporal Change, and Conservation Status of Tropical Seagrass Beds in Southeast Asia: 2000–2020 - Kenji Sudo; T. E. Angela L. Quiros; Anchana Prathep; Cao Van Luong; Hsing-Juh Lin; Japar Sidik Bujang; Jillian Lean Sim Ooi; Miguel D. Fortes; Muta Harah Zakaria; Siti Maryam Yaakub; Yi Mei Tan; Xiaoping Huang; et al. (Frontiers in Marine Science, 2021)
Although Southeast Asia is a hotspot of global seagrass diversity, there are considerable information gaps in the distribution of seagrass beds. Broad-scale seagrass distribution has not been updated in the global seagrass database by UNEP-WCMC since 2000, although studies on seagrasses have been undertaken intensively in each region. Here we analyze the recent distribution of tropical seagrass beds, their temporal changes, causes of decline and conservation status in Southeast Asia (plus southern mainland China, Taiwan and Ryukyu Island of Japan) using data collected after 2000. Based on the 195 literature published since 2000, we identified 1,259 point data and 1,461 polygon data showing the distribution of seagrass beds. A large discrepancy was found in the seagrass bed distribution between our updated data and the UNEP-WCMC database, mostly due to inaccurate and low resolution location information in the latter. Temporal changes in seagrass bed area analyzed for 68 sites in nine countries/regions demonstrated that more than 60% of seagrass beds declined at an average rate of 10.9% year –1 , whereas 20% of beds increased at an average rate of 8.1% year –1 , leading to an overall average decline of 4.7% year –1 . Various types of human-induced threats were reported as causes for the decline, including coastal development, fisheries/aquaculture, and natural factors such as typhoons and tsunamis. The percentage of seagrass beds covered with existing marine protected areas (MPAs) varied greatly among countries/regions, from less than 1% in Brunei Darussalam and Singapore to 100% in southern Japan. However, the degree of conservation regulation was not sufficient even in regions with higher MPA coverage. The percentage of seagrass beds within EBSAs (Ecologically and Biologically Significant Area determined by the Convention of Biological Diversity) was higher than that within MPAs because EBSAs cover a greater area than MPAs. Therefore, designating EBSAs as legally effective MPAs can greatly improve the conservation status of seagrass beds in Southeast Asia.

Anthropogenic Effects on Biogenic Secondary Organic Aerosol Formation - Li Xu; Lin Du; Narcisse T. Tsona; Maofa Ge (Advances in Atmospheric Sciences, 2021)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Lack of resemblance between Myhre syndrome and other “segmental progeroid” syndromes warrants restraint in applying this classification - Angela E. Lin; Nicola Brunetti-Pierri; Bert Callewaert; Valérie Cormier-Daire; Sofia Douzgou; T. Bernard Kinane; Mark E. Lindsay; Lois J. Starr (GeroScience, 2021)

Use of Exposomic Methods Incorporating Sensors in Environmental Epidemiology - Brett T. Doherty; Jeremy P. Koelmel; Elizabeth Z. Lin; Megan E. Romano; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2021)

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

Genetic diversity and life‐history traits of bonefish Albula spp. from the Red Sea - Collin T. Williams; Ashlie J. McIvor; Elizabeth M. Wallace; Yu‐Jia Lin; Michael L. Berumen (Journal of Fish Biology, 2021)
The management of bonefishes Albula spp. has been hindered by unresolved species distributions and a general lack of life‐history information. This study provides the first genetic species identifications of Albula spp. from the northern Indian Ocean. The roundjaw bonefish Albula glossodonta was documented in the Red Sea, and the smallscale bonefish A. oligolepis was identified in the Gulf of Aden with no evidence supporting sympatry. Estimates of genetic differentiation indicate three closely related lineages of A. glossodonta in the Red Sea, Indian Ocean and Pacific Ocean (Red Sea‐Pacific Ocean, F st = 0.295; Red Sea‐Seychelles, F st = 0.193; Pacific Ocean‐Seychelles, F st = 0.141). In addition, the authors provide the first life‐history information of Albula spp. in the Indian Ocean. Age‐based growth models of A. glossodonta from the Red Sea demonstrated statistically significant differences compared to previously published data from the Pacific Ocean. Spawning activity during winter months was derived from gonado‐somatic index values of A. glossodonta from the Red Sea and corresponded with spawning seasonality previously documented for the species in the Pacific Ocean. The results of this study aid in refining biogeographical uncertainties of Albula spp. and illustrate the importance of collecting regional growth information for subsequent management of A. glossodonta .

Preformulation Characterization of Griffithsin, a Biopharmaceutical Candidate for HIV Prevention - Lindsay F. Kramzer; Krystal T. Hamorsky; Phillip W. Graebing; Lin Wang; Joshua L. Fuqua; Nobuyuki Matoba; Amanda B. Lasnik; Bernard J. Moncla; Junmei Zhang; Kenneth E. Palmer; Lisa C. Rohan (AAPS PharmSciTech, 2021)

The stratigraphic significance of early Cambrian (Series 2, Stage 4) trilobites from the Smith Bay Shale near Freestone Creek, Kangaroo Island - J. B. Jago; C. J. Bentley; J. R. Paterson; J. D. Holmes; T. R. Lin; X. W. Sun (Australian Journal of Earth Sciences, 2021)

Application of plant metabarcoding to identify diverse honeybee pollen forage along an urban–agricultural gradient - Rodney T. Richardson; Tyler D. Eaton; Chia‐Hua Lin; Garrett Cherry; Reed M. Johnson; Douglas B. Sponsler (Molecular Ecology, 2021)
Understanding animal foraging ecology requires large sample sizes spanning broad environmental and temporal gradients. For pollinators, this has been hampered by the laborious nature of morphologically identifying pollen. Identifying pollen from urban environments is particularly difficult due to the presence of diverse ornamental species associated with consumer horticulture. Metagenetic pollen analysis represents a potential solution to this issue. Building upon prior laboratory and bioinformatic methods, we applied quantitative multilocus metabarcoding to characterize the foraging ecology of honeybee colonies situated in urban, suburban, mixed suburban–agricultural and rural agricultural sites in central Ohio, USA. In cross‐validating a subset of our metabarcoding results using microscopic palynology, we find strong concordance between the molecular and microscopic methods. Our results suggest that forage from the agricultural site exhibited decreased taxonomic diversity and temporal turnover relative to the urban and suburban sites, though the generalization of this observation will require replication across additional sites and cities. Our work demonstrates the power of honeybees as environmental samplers of floral community composition at large spatial scales, aiding in the distinction of taxa characteristically associated with urban or agricultural land use from those distributed ubiquitously across the sampled landscapes. Observed patterns of high forage diversity and compositional turnover in our more urban sites are likely reflective of the fine‐grain heterogeneity and high beta diversity of urban floral landscapes at the scale of honeybee foraging. This provides guidance for future studies investigating how relationships between urbanization and measures of pollinator health are mediated by variation in floral resource dynamics across landscapes.

Large-scale control on the frequency of tropical cyclones and seeds: a consistent relationship across a hierarchy of global atmospheric models - Tsung-Lin Hsieh; Gabriel A. Vecchi; Wenchang Yang; Isaac M. Held; Stephen T. Garner (Climate Dynamics, 2020)
A diagnostic framework is developed to explain the response of tropical cyclones (TCs) to climate in high-resolution global atmospheric models having different complexity of boundary conditions. The framework uses vortex dynamics to identify the large-scale control on the evolution of TC precursors—first non-rotating convective clusters and then weakly rotating seeds. In experiments with perturbed sea surface temperature (SST) and $$\hbox {CO}_2$$ CO 2 concentration from the historical values, the response of TCs follows the response of seeds. The distribution of seeds is explained by the distribution of the non-rotating convective clusters multiplied by a probability that they transition to seeds. The distribution of convective clusters is constrained by the large-scale vertical velocity and is verified in aquaplanet experiments with shifting Inter tropical Convergence Zones. The probability of transition to seeds is constrained by the large-scale vorticity via an analytical function, representing the relative importance between vortex stretching and vorticity advection, and is verified in aquaplanet experiments with uniform SST. The consistency between seed and TC responses breaks down substantially when the realistic SST is perturbed such that the spatial gradient is significantly enhanced or reduced. In such cases, the difference between the responses is explained by a change in the ventilation index, which influences the fraction of seeds that develop into TCs. The proposed TC-climate relationship serves as a framework to explain the diversity of TC projection across models and forcing scenarios.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Load Distribution at the Patellofemoral Joint During Walking - Lucas T. Thomeer; Yi-Chung Lin; Marcus G. Pandy (Annals of Biomedical Engineering, 2020)

Three lessons conservation science can learn from the COVID‐19 pandemic - Rachel T. Buxton; Jordanna N. Bergman; Hsien‐Yung Lin; Allison D. Binley; Stephanie Avery‐Gomm; Richard Schuster; Dominique G. Roche; Joseph R. Bennett (Conservation Biology, 2020)
Article impact statement : COVID‐19 has demonstrated the need to optimize research activity, convey the gravity of loss, and reevaluate merit in conservation science.

Embryonic gene expression altered by maternal exposure to air pollution in rats - Zheng Li; Jianqing Ma; Youxi Lin; Jianxiong Shen; Zhanyong Wu; Matthew T. V. Chan; William K. K. Wu (Environmental Science and Pollution Research, 2020)

Climate change considerations are fundamental to management of deep‐sea resource extraction - Lisa A. Levin; Chih‐Lin Wei; Daniel C. Dunn; Diva J. Amon; Oliver S. Ashford; William W. L. Cheung; Ana Colaço; Carlos Dominguez‐Carrió; Elva G. Escobar; Harriet R. Harden‐Davies; Jeffrey C. Drazen; Khaira Ismail; et al. (Global Change Biology, 2020)
Climate change manifestation in the ocean, through warming, oxygen loss, increasing acidification, and changing particulate organic carbon flux (one metric of altered food supply), is projected to affect most deep‐ocean ecosystems concomitantly with increasing direct human disturbance. Climate drivers will alter deep‐sea biodiversity and associated ecosystem services, and may interact with disturbance from resource extraction activities or even climate geoengineering. We suggest that to ensure the effective management of increasing use of the deep ocean (e.g., for bottom fishing, oil and gas extraction, and deep‐seabed mining), environmental management and developing regulations must consider climate change. Strategic planning, impact assessment and monitoring, spatial management, application of the precautionary approach, and full‐cost accounting of extraction activities should embrace climate consciousness. Coupled climate and biological modeling approaches applied in the water and on the seafloor can help accomplish this goal. For example, Earth‐System Model projections of climate‐change parameters at the seafloor reveal heterogeneity in projected climate hazard and time of emergence (beyond natural variability) in regions targeted for deep‐seabed mining. Models that combine climate‐induced changes in ocean circulation with particle tracking predict altered transport of early life stages (larvae) under climate change. Habitat suitability models can help assess the consequences of altered larval dispersal, predict climate refugia, and identify vulnerable regions for multiple species under climate change. Engaging the deep observing community can support the necessary data provisioning to mainstream climate into the development of environmental management plans. To illustrate this approach, we focus on deep‐seabed mining and the International Seabed Authority, whose mandates include regulation of all mineral‐related activities in international waters and protecting the marine environment from the harmful effects of mining. However, achieving deep‐ocean sustainability under the UN Sustainable Development Goals will require integration of climate consideration across all policy sectors.

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

DNA methylation and histone acetylation changes to cytochrome P450 2E1 regulation in normal aging and impact on rates of drug metabolism in the liver - Mohamad M. Kronfol; Fay M. Jahr; Mikhail G. Dozmorov; Palak S. Phansalkar; Lin Y. Xie; Karolina A. Aberg; MaryPeace McRae; Elvin T. Price; Patricia W. Slattum; Philip M. Gerk; Joseph L. McClay (GeroScience, 2020)

The emission of volatile halocarbons by seaweeds and their response towards environmental changes - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Emma C. Leedham Elvidge; Gill Malin; William T. Sturges (Journal of Applied Phycology, 2020)

Alpine grassland plants grow earlier and faster but biomass remains unchanged over 35 years of climate change - Hao Wang; Huiying Liu; Guangmin Cao; Zhiyuan Ma; Yikang Li; Fawei Zhang; Xia Zhao; Xinquan Zhao; Lin Jiang; Nathan J. Sanders; Aimée T. Classen; Jin‐Sheng He (Ecology Letters, 2020)
Satellite data indicate significant advancement in alpine spring phenology over decades of climate warming, but corresponding field evidence is scarce. It is also unknown whether this advancement results from an earlier shift of phenological events, or enhancement of plant growth under unchanged phenological pattern. By analyzing a 35‐year dataset of seasonal biomass dynamics of a Tibetan alpine grassland, we show that climate change promoted both earlier phenology and faster growth, without changing annual biomass production. Biomass production increased in spring due to a warming‐induced earlier onset of plant growth, but decreased in autumn due mainly to increased water stress. Plants grew faster but the fast‐growing period shortened during the mid‐growing season. These findings provide the first in situ evidence of long‐term changes in growth patterns in alpine grassland plant communities, and suggest that earlier phenology and faster growth will jointly contribute to plant growth in a warming climate.

Protein Arginine Methyltransferases in Cardiovascular and Neuronal Function - Alexandre Couto e Silva; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Garrett A. Clemons; HarLee E. Possoit; Mychal S. Grames; Chih-Feng Lien; Alireza Minagar; Reggie Hui-Chao Lee; Adam Frankel; Hung Wen Lin (Molecular Neurobiology, 2020)

Experimental and Analytical Investigations of the Effect of Hole Size on Borehole Breakout Geometries for Estimation of In Situ Stresses - H. Lin; J. Oh; I. Canbulat; T. R. Stacey (Rock Mechanics and Rock Engineering, 2020)

Managing water quality in a river basin with uncertainty - H.-W. Chen; W.-Y. Chen; C.-T. Wang; Y.-H. Lin; M.-J. Deng; C.-Y. Chiang (International Journal of Environmental Science and Technology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Inflammation-related genes are associated with epigenetic aging in HIV - Erin E. Sundermann; Mariam A. Hussain; David J. Moore; Steven Horvath; David T. S. Lin; Michael S. Kobor; Andrew Levine (Journal of NeuroVirology, 2019)

Transgenic maize phosphoenolpyruvate carboxylase alters leaf–atmosphere CO2 and 13CO2 exchanges in Oryza sativa - Rita Giuliani; Shanta Karki; Sarah Covshoff; Hsiang-Chun Lin; Robert A. Coe; Nuria K. Koteyeva; Marc A. Evans; W. Paul Quick; Susanne von Caemmerer; Robert T. Furbank; Julian M. Hibberd; Gerald E. Edwards; et al. (Photosynthesis Research, 2019)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Following legume establishment, microbial and chemical associations facilitate improved productivity in degraded grasslands - Jiqiong Zhou; Fengge Zhang; Yunqian Huo; Gail W. T. Wilson; Adam B. Cobb; Xixi Xu; Xue Xiong; Lin Liu; Yingjun Zhang (Plant and Soil, 2019)

Crops For the Future (CFF): an overview of research efforts in the adoption of underutilised species - Peter J. Gregory; Sean Mayes; Chai Hui Hui; Ebrahim Jahanshiri; Advina Julkifle; Giva Kuppusamy; Ho Wai Kuan; Tan Xin Lin; Festo Massawe; T. A. S. T. M. Suhairi; Sayed N. Azam-Ali (Planta, 2019)

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Tidal variability in the Hong Kong region - Adam T. Devlin; Jiayi Pan; Hui Lin (Ocean Science, 2019)
Mean sea level (MSL) is rising worldwide, and correlated changes in ocean tides are also occurring. This combination may influence future extreme sea levels, possibly increasing coastal inundation and nuisance flooding events in sensitive regions. Analyses of a set of tide gauges in Hong Kong reveal complex tidal behavior. Most prominent in the results are strong correlations of MSL variability to tidal variability over the 31-year period of 1986–2016; these tidal anomaly correlations (TACs) express the sensitivity of tidal amplitudes and phases (M2, S2, K1, O1) to MSL fluctuations and are widely observed across the Hong Kong region. At a few important harbor locations, time series of approximations of the parameter δ-HAT, computed from combinations of the major tidal constituents, are found to be highly sensitive to MSL variability, which may further increase local flood levels under future MSL rise. Other open-water locations in Hong Kong only show TACs for some individual tidal constituents but not for combined tidal amplitudes, suggesting that the dynamics in enclosed harbor areas may be partially frequency dependent and related to resonance or frictional changes. We also observe positive correlations of the fluctuations of diurnal (D1) tides to semidiurnal (D2) tides at most locations in the region, which may lead to further amplified tidal ranges under MSL. It is demonstrated here that tidal changes in the Hong Kong coastal waters may be important in combination with MSL rise in impacting future total water levels.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Integration of Food Animal Residue Avoidance Databank (FARAD) empirical methods for drug withdrawal interval determination with a mechanistic population-based interactive physiologically based pharmacokinetic (iPBPK) modeling platform: example for flunixin meglumine administration - Miao Li; Yi-Hsien Cheng; Jason T. Chittenden; Ronald E. Baynes; Lisa A. Tell; Jennifer L. Davis; Thomas W. Vickroy; Jim E. Riviere; Zhoumeng Lin (Archives of Toxicology, 2019)

Long-term Nutrient Fertilization Increased Soil Carbon Storage in California Grasslands - Yang Lin; Eric W. Slessarev; Scott T. Yehl; Carla M. D’Antonio; Jennifer Y. King (Ecosystems, 2019)

The return of the frogs: The importance of habitat refugia in maintaining diversity during a disease outbreak - Donald T. McKnight; Monal M. Lal; Deborah S. Bower; Lin Schwarzkopf; Ross A. Alford; Kyall R. Zenger (Molecular Ecology, 2019)
Recent decades have seen the emergence and spread of numerous infectious diseases, often with severe negative consequences for wildlife populations. Nevertheless, many populations survive the initial outbreaks, and even undergo recoveries. Unfortunately, the long‐term effects of these outbreaks on host population genetics are poorly understood; to increase this understanding, we examined the population genetics of two species of rainforest frogs ( Litoria nannotis and Litoria serrata ) that have largely recovered from a chytridiomycosis outbreak at two national parks in the Wet Tropics of northern Australia. At the wetter, northern park there was little evidence of decreased genetic diversity in either species, and all of the sampled sites had high minor allele frequencies (mean MAF = 0.230–0.235), high heterozygosity (0.318–0.325), and few monomorphic markers (1.4%–4.0%); however, some recovered L. nannotis populations had low N e values (59.3–683.8) compared to populations that did not decline during the outbreak (1,537.4–1,756.5). At the drier, southern park, both species exhibited lower diversity (mean MAF = 0.084–0.180; heterozygosity = 0.126–0.257; monomorphic markers = 3.7%–43.5%; N e = 18.4–676.1). The diversity patterns in this park matched habitat patterns, with both species having higher diversity levels and fewer closely related individuals at sites with higher quality habitat. These patterns were more pronounced for L. nannotis, which has lower dispersal rates than L. serrata . These results suggest that refugia with high quality habitat are important for retaining genetic diversity during disease outbreaks, and that gene flow following disease outbreaks is important for re‐establishing diversity in populations where it was reduced.

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

Implementation of multiplex PCR diagnostics for gastrointestinal pathogens linked to increase of notified Shiga toxin-producing Escherichia coli cases in Norway, 2007–2017 - Gaute Reier Jenssen; Lamprini Veneti; Heidi Lange; Line Vold; Umaer Naseer; Lin T. Brandal (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Modulation of the southern Indian Ocean dipole on the impact of El Niño–Southern Oscillation on Australian summer rainfall - Hainan Gong; Wen Zhou; Wen Chen; Lin Wang; Marco Y.‐T. Leung; Paxson K.‐Y. Cheung; Yue Zhang (International Journal of Climatology, 2019)
This study investigates the modulation of the southern Indian Ocean dipole (SIOD) upon the impacts of the El Niño–Southern Oscillation (ENSO) on Australian summer rainfall (ASR) on an inter‐annual timescale. First the SIOD is identified as an important factor influencing rainfall anomalies over northeastern Australia via a zonal vertical circulation spanning from the southern Indian Ocean (SIO) to northern Australia. When ENSO and the SIOD are out of phase, the El Niño‐induced anticyclonic and convection anomalies shift eastwards to Australia and induce pronounced negative rainfall anomalies in northern Australia. When ENSO and the SIOD are in phase, the anticyclonic and convection anomalies extend westwards and generate an anomalous zonal vertical circulation, inducing positive rainfall anomalies in northeastern Australia. These different shifts in the circulation and rainfall anomalies with the two types of ENSO–SIOD occurrences are essentially attributed to the opposite effects of the different phases of SIOD events. The out‐of‐phase and in‐phase combinations of ENSO and the SIOD also largely form the dominant patterns of ASR variation. The significant influence of the SIOD on ASR indicates that the phase of the SIOD should be taken into account in the prediction of austral summer climate over Australia.

A differential k-mer analysis pipeline for comparing RNA-Seq transcriptome and meta-transcriptome datasets without a reference - Chon-Kit Kenneth Chan; Nedeljka Rosic; Michał T. Lorenc; Paul Visendi; Meng Lin; Paulina Kaniewska; Brett J. Ferguson; Peter M. Gresshoff; Jacqueline Batley; David Edwards (Functional & Integrative Genomics, 2019)

Expression of Aβ42, τ-Protein, p16, p53 in Buccal Epithelium: Prospects for Use in the Diagnostics of Alzheimer’s Disease and Rate of Aging - V. A. Zuev; A. S. Dyatlova; N. S. Lin’kova; T. V. Kvetnaya (Bulletin of Experimental Biology and Medicine, 2019)

Underestimated ecosystem carbon turnover time and sequestration under the steady state assumption: A perspective from long‐term data assimilation - Rong Ge; Honglin He; Xiaoli Ren; Li Zhang; Guirui Yu; T. Luke Smallman; Tao Zhou; Shi‐Yong Yu; Yiqi Luo; Zongqiang Xie; Silong Wang; Huimin Wang; et al. (Global Change Biology, 2019)
It is critical to accurately estimate carbon (C) turnover time as it dominates the uncertainty in ecosystem C sinks and their response to future climate change. In the absence of direct observations of ecosystem C losses, C turnover times are commonly estimated under the steady state assumption ( SSA ), which has been applied across a large range of temporal and spatial scales including many at which the validity of the assumption is likely to be violated. However, the errors associated with improperly applying SSA to estimate C turnover time and its covariance with climate as well as ecosystem C sequestrations have yet to be fully quantified. Here, we developed a novel model‐data fusion framework and systematically analyzed the SSA ‐induced biases using time‐series data collected from 10 permanent forest plots in the eastern China monsoon region. The results showed that (a) the SSA significantly underestimated mean turnover times ( MTT s) by 29%, thereby leading to a 4.83‐fold underestimation of the net ecosystem productivity ( NEP ) in these forest ecosystems, a major C sink globally; (b) the SSA ‐induced bias in MTT and NEP correlates negatively with forest age, which provides a significant caveat for applying the SSA to young‐aged ecosystems; and (c) the sensitivity of MTT to temperature and precipitation was 22% and 42% lower, respectively, under the SSA . Thus, under the expected climate change, spatiotemporal changes in MTT are likely to be underestimated, thereby resulting in large errors in the variability of predicted global NEP . With the development of observation technology and the accumulation of spatiotemporal data, we suggest estimating MTT s at the disequilibrium state via long‐term data assimilation, thereby effectively reducing the uncertainty in ecosystem C sequestration estimations and providing a better understanding of regional or global C cycle dynamics and C‐climate feedback.

Quantitative multi‐locus metabarcoding and waggle dance interpretation reveal honey bee spring foraging patterns in Midwest agroecosystems - Rodney T. Richardson; Hailey R. Curtis; Emma G. Matcham; Chia‐Hua Lin; Sreelakshmi Suresh; Douglas B. Sponsler; Luke E. Hearon; Reed M. Johnson (Molecular Ecology, 2019)
We explored the pollen foraging behaviour of honey bee colonies situated in the corn and soybean dominated agroecosystems of central Ohio over a month‐long period using both pollen metabarcoding and waggle dance inference of spatial foraging patterns. For molecular pollen analysis, we developed simple and cost‐effective laboratory and bioinformatics methods. Targeting four plant barcode loci (ITS2, rbcL , trnL and trnH ), we implemented metabarcoding library preparation and dual‐indexing protocols designed to minimize amplification biases and index mistagging events. We constructed comprehensive, curated reference databases for hierarchical taxonomic classification of metabarcoding data and used these databases to train the metaxa 2 DNA sequence classifier. Comparisons between morphological and molecular palynology provide strong support for the quantitative potential of multi‐locus metabarcoding. Results revealed consistent foraging habits between locations and show clear trends in the phenological progression of honey bee spring foraging in these agricultural areas. Our data suggest that three key taxa, woody Rosaceae such as pome fruits and hawthorns, Salix , and Trifolium provided the majority of pollen nutrition during the study. Spatially, these foraging patterns were associated with a significant preference for forests and tree lines relative to herbaceous land cover and nonflowering crop fields.

Does Regional Development Influence Sedimentary Blue Carbon Stocks? A Case Study From Three Australian Estuaries - Stephen Conrad; Dylan R. Brown; Paula Gomez Alvarez; Bronte Bates; Nizam Ibrahim; Alex Reid; Luciana Silva Monteiro; Daniela A. Silva; Lea T. Mamo; Jacob R. Bowtell; Huang An Lin; Nathaniel L. Tolentino; et al. (Frontiers in Marine Science, 2019)

Nonparametric dynamical model of cardiorespiratory responses at the onset and offset of treadmill exercises - Hairong Yu; Lin Ye; Ganesh R. Naik; Rong Song; Hung T. Nguyen; Steven W. Su (Medical & Biological Engineering & Computing, 2018)

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Pharmacodynamic and Pharmacokinetic Properties of AFPep, a Novel Peptide for the Treatment of Breast Cancer - J. A. Bennett; W. Mansouri; Q. Lin; P. Feustel; T. T. Andersen (International Journal of Peptide Research and Therapeutics, 2018)

Kinetics of atmospheric reactions of 4-chloro-1-butene - Jianqiang Zhu; Narcisse T. Tsona; Lin Du (Environmental Science and Pollution Research, 2018)

An Attempt to Find a Suitable Biomass for Biochar-Based Polypropylene Biocomposites - Oisik Das; Nam Kyeun Kim; Mikael S. Hedenqvist; Richard J. T. Lin; Ajit K. Sarmah; Debes Bhattacharyya (Environmental Management, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Fine-Mode Aerosol Loading Over a Sub-Sahel Location and Its Relation with the West African Monsoon - Okechukwu K. Nwofor; Victor N. Dike; Zhaohui Lin; Rachel T. Pinker; Nnaemeka D. Onyeuwaoma (Aerosol Science and Engineering, 2018)

Intraspecific aggregation and soil heterogeneity: competitive interactions of two clonal plants with contrasting spatial architecture - Wei Xue; Lin Huang; Fei-Hai Yu; T. Martijn Bezemer (Plant and Soil, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Delivery of adjuvant chemotherapy among stage III colon cancer patients at a public versus private hospital in New York City - Daniel Lin; Judith D. Goldberg; Tsivia Hochman; Benjamin A. Levinson; Maria Khan; Elliot Newman; Lawrence P. Leichman; Heather T. Gold (Cancer Causes & Control, 2018)

Complex inter‐island colonization and peripatric founder speciation promote diversification of flightless Pachyrhynchus weevils in the Taiwan–Luzon volcanic belt - Hui‐Yun Tseng; Wen‐San Huang; Ming‐Luen Jeng; Reagan Joseph T. Villanueva; Olga M. Nuñeza; Chung‐Ping Lin (Journal of Biogeography, 2018)
Aim We investigated the spatial and temporal patterns of diversification among colourful and flightless weevils, the Pachyrhynchus orbifer complex, to test the stepping‐stone hypothesis of colonization across the Taiwan–Luzon volcanic belt. Location Southeast Asia. Methods The phylogeny of the P. orbifer complex was reconstructed from a multi‐locus data set of mitochondrial and nuclear genes using maximum likelihood in RAxML and Bayesian inference in MRBAYES. Likelihood‐based tests in CONSEL were used to evaluate alternative tree topologies. Divergence times were estimated in beast based on a range of mutation rates. Ancestral range and biogeographical history were reconstructed using Bayesian binary MCMC ( BBM ) methods in RASP and in BioGeoBEARS. Demographic histories were inferred using the extended Bayesian skyline plot ( EBSP ). Species boundaries were tested using BPP. Results The phylogeny of the P. orbifer complex indicated strong support for seven reciprocally monophyletic lineages grouped by current island boundaries (Camiguin, Fuga, Dalupiri, Calayan, Babuyan, Orchid and Yaeyama Islands), except for a sister Green + Itbayat lineage. Complex and stochastic colonization of P. orbifer was inferred to have involved both northward and southward directions with short‐ and long‐distance dispersal events, which are strongly inconsistent with the strict stepping‐stone hypothesis. Divergence time estimates for all extant island lineages ( c . 3 Myr) of the islands. The statistically delimited seven cryptic species imply that the diversity of Pachyrhynchus from small peripheral islands continues to be largely under‐estimated. Main conclusions The non‐linear, more complex spatial and temporal settings of the archipelago and stochastic dispersal were probable key factors shaping the colonization history of the P. orbifer complex. Speciation of the P. orbifer complex may have occurred only between islands, indicating that peripatric speciation through the founders of stochastic dispersals was the major evolutionary driver.

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of emerging infectious diseases on host population genetics: a review - Donald T. McKnight; Lin Schwarzkopf; Ross A. Alford; Deborah S. Bower; Kyall R. Zenger (Conservation Genetics, 2017)

Fighting an uphill battle: the recovery of frogs in Australia's Wet Tropics - Donald T. McKnight; Ross A. Alford; Conrad J. Hoskin; Lin Schwarzkopf; Sasha E. Greenspan; Kyall R. Zenger; Deborah S. Bower (Ecology, 2017)

Identification of Peptide AEDG in the Polypeptide Complex of the Pineal Gland - V. Kh. Khavinson; A. T. Kopylov; B. V. Vaskovsky; G. A. Ryzhak; N. S. Lin’kova (Bulletin of Experimental Biology and Medicine, 2017)

Acclimation of bloom‐forming and perennial seaweeds to elevated p CO 2 conserved across levels of environmental complexity - Dong Xu; Charlotte‐Elisa Schaum; Fan Lin; Ke Sun; James R. Munroe; Xiao W. Zhang; Xiao Fan; Lin H. Teng; Yi T. Wang; Zhi M. Zhuang; Naihao Ye (Global Change Biology, 2017)
Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO 2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO 2 levels ranging from 400 to 2,000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO 2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds.

Development of a two-stage washing and biodegradation system to remediate octachlorinated dibenzo-p-dioxin-contaminated soils - J. L. Lin; C. D. Dong; C. W. Chen; S. H. Chen; T. E. Hsieh; C. M. Kao (International Journal of Environmental Science and Technology, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Risk factors and outcome of levofloxacin-resistant Elizabethkingia meningoseptica bacteraemia in adult patients in Taiwan - Y.-C. Huang; Y.-W. Huang; Y.-T. Lin; F.-D. Wang; Y.-J. Chan; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Nephroprotective Effect of EDL Peptide at Acute Injury of Kidneys of Different Genesis - I. I. Zamorskii; T. S. Shchudrova; N. S. Lin’kova; T. E. Nichik; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Endometriosis and risk of ovarian and endometrial cancers in a large prospective cohort of U.S. nurses - Elizabeth M. Poole; Wayne T. Lin; Marina Kvaskoff; Immaculata De Vivo; Kathryn L. Terry; Stacey A. Missmer (Cancer Causes & Control, 2017)

Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico - Carol T. Stuart; Solange Brault; Gilbert T. Rowe; Chih‐Lin Wei; Martine Wagstaff; Craig R. McClain; Michael A. Rex (Journal of Biogeography, 2017)
Aim To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location Western Gulf of Mexico. Methods We used A. Baselga's (2010, Global Ecology and Biogeography, 19 , 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon ( POC ) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography , 33 , 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Effect of Polypeptides on Cell Proliferation and Apoptosis during Aging - A.P. Ryzhak; N. I. Chalisova; N. S. Lin’kova; T. E. Nichik; A.V. Dudkov; N. V. Kolchina; G. A. Ryzhak; R. I. Khalimov (Bulletin of Experimental Biology and Medicine, 2017)

Transcriptomic imprints of adaptation to fresh water: parallel evolution of osmoregulatory gene expression in the Alewife - Jonathan P. Velotta; Jill L. Wegrzyn; Samuel Ginzburg; Lin Kang; Sergiusz Czesny; Rachel J. O'Neill; Stephen D. McCormick; Pawel Michalak; Eric T. Schultz (Molecular Ecology, 2017)
Comparative approaches in physiological genomics offer an opportunity to understand the functional importance of genes involved in niche exploitation. We used populations of Alewife ( Alosa pseudoharengus ) to explore the transcriptional mechanisms that underlie adaptation to fresh water. Ancestrally anadromous Alewives have recently formed multiple, independently derived, landlocked populations, which exhibit reduced tolerance of saltwater and enhanced tolerance of fresh water. Using RNA ‐seq, we compared transcriptional responses of an anadromous Alewife population to two landlocked populations after acclimation to fresh (0 ppt) and saltwater (35 ppt). Our results suggest that the gill transcriptome has evolved in primarily discordant ways between independent landlocked populations and their anadromous ancestor. By contrast, evolved shifts in the transcription of a small suite of well‐characterized osmoregulatory genes exhibited a strong degree of parallelism. In particular, transcription of genes that regulate gill ion exchange has diverged in accordance with functional predictions: freshwater ion‐uptake genes (most notably, the ‘freshwater paralog’ of Na + /K + ‐ ATP ase α‐subunit) were more highly expressed in landlocked forms, whereas genes that regulate saltwater ion secretion (e.g. the ‘saltwater paralog’ of NKA α) exhibited a blunted response to saltwater. Parallel divergence of ion transport gene expression is associated with shifts in salinity tolerance limits among landlocked forms, suggesting that changes to the gill's transcriptional response to salinity facilitate freshwater adaptation.

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

Limited diversity associated with duplicated class II MHC-DRB genes in the red squirrel population in the United Kingdom compared with continental Europe - Keith T. Ballingall; Angeline McIntyre; Zhenzhen Lin; Naomi Timmerman; Erik Matthysen; Peter W.W. Lurz; Lynsey Melville; Amy Wallace; Anna L. Meredith; Claudia Romeo; Lucas A. Wauters; Anthony W. Sainsbury; et al. (Conservation Genetics, 2016)

A prognostic model for advanced colorectal neoplasia recurrence - Lin Liu; Karen Messer; John A. Baron; David A. Lieberman; Elizabeth T. Jacobs; Amanda J. Cross; Gwen Murphy; Maria Elena Martinez; Samir Gupta (Cancer Causes & Control, 2016)

Kin-biased conspecific brood parasitism in a native Mandarin duck population - Ye Gong; Rebecca T. Kimball; Colette St. Mary; Xiang Cui; Lin Wang; Yunlei Jiang; Haitao Wang (Journal of Ornithology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Stephen T. Spagnol; Wei-Chun Lin; Elizabeth A. Booth; Benoit Ladoux; Hillard M. Lazarus; Kris Noel Dahl (Annals of Biomedical Engineering, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Differentiation in development of benzimidazole resistance in Colletotrichum gloeosporioides complex populations from strawberry and grape hosts - T. Lin; X. F. Xu; D. J. Dai; H. J. Shi; H. D. Wang; C. Q. Zhang (Australasian Plant Pathology, 2016)

Genomic variability and molecular evolution of Asian isolates of sugarcane streak mosaic virus - Shan-Shan Liang; Olufemi J. Alabi; Mona B. Damaj; Wei-Lin Fu; Sheng-Ren Sun; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov; San-Ji Gao (Archives of Virology, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Macrobenthos in the central Arabian Gulf: a reflection of climate extremes and variability - Chih-Lin Wei; Gilbert T. Rowe; Mohsin Al-Ansi; Ibrahim Al-Maslamani; Yousria Soliman; Nehad Nour El-Din; Ibrahim S. Al-Ansari; Ismail Al-Shaikh; Antonietta Quigg; Clifton Nunnally; Mohamed A. Abdel-Moati (Hydrobiologia, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

The impact of global budgeting on health service utilization, health care expenditures, and quality of care among patients with pneumonia in Taiwan - C.-Y. Lin; T. Ma; C.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Dopaminergic genetic variation moderates the effect of nicotine on cigarette reward - Paul T. Harrell; Hui-Yi Lin; Jong Y. Park; Melissa D. Blank; David J. Drobes; David E. Evans (Psychopharmacology, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

A biodegradable ocular implant for long-term suppression of intraocular pressure - Xu Wen Ng; Kerh Lin Liu; Amutha Barathi Veluchamy; Nyein Chan Lwin; Tina T. Wong; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2015)

Peptides Restore Functional State of the Kidneys During Cisplatin-Induced Acute Renal Failure - I. I. Zamorskii; T. S. Shchudrova; N. S. Lin’kova; T. E. Nichik; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2015)

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Erratum to: Reliability of Postmortem Fentanyl Concentrations in Determining the Cause of Death - James R. Gill; Peter T. Lin; Lewis Nelson (Journal of Medical Toxicology, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Robust Endoplasmic Reticulum-Associated Degradation of Rhodopsin Precedes Retinal Degeneration - Wei-Chieh Chiang; Heike Kroeger; Sanae Sakami; Carissa Messah; Douglas Yasumura; Michael T. Matthes; Judith A. Coppinger; Krzysztof Palczewski; Matthew M. LaVail; Jonathan H. Lin (Molecular Neurobiology, 2015)

The juxtamembrane sequence of the Hepatitis C virus polymerase can affect RNA synthesis and inhibition by allosteric polymerase inhibitors - Y. Wen; X. Lin; B. Fan; C. T. Ranjith-Kumar; C. C. Kao (Virus Genes, 2015)

Stress hormone metabolites predict overwinter survival in yellow-bellied marmots - Tina W. Wey; Lawrence Lin; Marilyn L. Patton; Daniel T. Blumstein (acta ethologica, 2015)

Peptide Regulation of Cells Renewal Processes in Kidney Tissue Cultures from Young and Old Animals - N. I. Chalisova; N. S. Lin’kova; T. E. Nichik; A. P. Ryzhak; A. V. Dudkov; G. A. Ryzhak (Bulletin of Experimental Biology and Medicine, 2015)

Mechanisms underlying local functional and phylogenetic beta diversity in two temperate forests - Xugao Wang; Thorsten Wiegand; Nathan G. Swenson; Amy T. Wolf; Robert W. Howe; Zhanqing Hao; Fei Lin; Ji Ye; Zuoqiang Yuan (Ecology, 2015)
Although trait information has been widely used to explore underlying mechanisms of forest community structure, most studies have focused on local patterns of phylogenetic or functional alpha diversity. Investigations of functional beta diversity, on the other hand, have not been conducted at local scales in a spatially explicit way. In this study, we provide a powerful methodology based on recent advances in spatial point pattern analysis using fully mapped data of large and small trees in two large temperate forest plots. This approach allowed us to assess the relative importance of different ecological processes and mechanisms for explaining patterns of local phylogenetic and functional beta diversity. For both forests and size classes, we found a clear hierarchy of scales: habitat filtering accounted for patterns of phylogenetic and functional beta diversity at larger distances (150–250 m), dispersal limitation accounted for the observed decline in beta diversity at distances below 150 m, and species interactions explained small departures from functional and phylogenetic beta diversity at the immediate plant‐neighborhood scale (below 20 m). Thus, both habitat filtering and dispersal limitation influenced the observed patterns in phylogenetic and functional beta diversity at local scales. This result contrasts with a previous study from the same forests, where dispersal limitation alone approximated the observed species beta diversity for distances up to 250 m. In addition, species interactions were relatively unimportant for predicting phylogenetic and functional beta diversity. Our analysis suggests that phylogenetic and functional beta diversity can provide insights into the mechanisms of local community assembly that are missed by studies focusing exclusively on species beta diversity.

Preclinical Pharmacokinetic/Pharmacodynamic Modeling and Simulation in the Pharmaceutical Industry: An IQ Consortium Survey Examining the Current Landscape - Edgar Schuck; Tonika Bohnert; Arijit Chakravarty; Valeriu Damian-Iordache; Christopher Gibson; Cheng-Pang Hsu; Tycho Heimbach; Anu Shilpa Krishnatry; Bianca M Liederer; Jing Lin; Tristan Maurer; Jerome T Mettetal; et al. (The AAPS Journal, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Establishment of a novel, eco-friendly transgenic pig model using porcine pancreatic amylase promoter-driven fungal cellulase transgenes - Y. S. Lin; C. C. Yang; C. C. Hsu; J. T. Hsu; S. C. Wu; C. J. Lin; W. T. K. Cheng (Transgenic Research, 2015)

Role of Peptide Bond in the Realization of Biological Activity of Short Peptides - V. Kh. Khavinson; S. I. Tarnovskaya; N. S. Lin’kova; N. A. Chervyakova; T. E. Nichik; E. V. Elashkina; N. I. Chalisova (Bulletin of Experimental Biology and Medicine, 2015)

Chelator-enhanced phytoextraction of copper and zinc by sunflower, Chinese cabbage, cattails and reeds - T. Y. Yeh; C. L. Lin; C. F. Lin; C. C. Chen (International Journal of Environmental Science and Technology, 2015)

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study - C.-Y. Lai; T.-Y. Yang; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

High seroprevalence of human herpesvirus type 8 in patients with hepatocellular carcinoma - C.-C. Su; K.-C. Tseng; M.-N. Lin; T.-C. Hsieh; T.-Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Responsiveness of cardiometabolic-related microbiota to diet is influenced by host genetics - Annalouise O’Connor; Pamela M. Quizon; Jody E. Albright; Fred T. Lin; Brian J. Bennett (Mammalian Genome, 2014)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Orexins (hypocretins) contribute to fear and avoidance in rats exposed to a single episode of footshocks - Xiaoyu Chen; Huiying Wang; Zhang Lin; Sa Li; Yonghui Li; Hugo T. Bergen; Maria E. Vrontakis; Gilbert J. Kirouac (Brain Structure and Function, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Nanomedicine for glaucoma: sustained release latanoprost offers a new therapeutic option with substantial benefits over eyedrops - Tina T. Wong; Gary D. Novack; Jayaganesh V. Natarajan; Ching Lin Ho; Hla M. Htoon; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Hopping out of Mindanao: Miocene‐Pliocene geological processes and cross‐island dispersal as major drivers of diversity for Philippine treehoppers - Yong‐Chao Su; Jo‐Fan Wang; Reagan Joseph T. Villanueva; Olga M. Nuñeza; Chung‐Ping Lin (Journal of Biogeography, 2014)
Aim We investigated the biogeographical history of an endemic Philippine treehopper, Pyrgonota bifoliata (Membracidae), to test the effect of Neogene geological events and Pleistocene climate change in generating speciation within the Philippines. Location The Philippine archipelago. Methods Phylogenies were reconstructed based on the mitochondrial cytochrome c oxidase I subunit ( cox1 ) and nuclear wingless ( wg ) genes using maximum parsimony, maximum likelihood and Bayesian criteria. Divergence times were estimated in beast based on a range of mutation rates. Ancestral ranges were reconstructed using rasp (Reconstruct Ancestral State in Phylogenies) and Bayesian stochastic search variable selection (BSSVS). Species boundaries were tested using the Bayesian general mixed Yule coalescent ( bGMYC ) and Bayesian phylogenetic and phylogeography (BPP) methods. Results Pyrgonota bifoliata showed one of the lowest levels of between‐Pleistocene island genetic variation among all the taxa examined. Most Pleistocene aggregate island complex ( PAIC ) lineages and extant P. bifoliata originated before the onset of the first extensive Pleistocene glacial cycle. Ancestral P. bifoliata originated in the late Miocene from Mindanao, followed by a sequential northwards colonization of the Visayan Islands and Luzon in the Pliocene–early Pleistocene, which coincided with the spatial reorganization of the Philippines. The statistically delimited nine provisional species of what we now view as the P. bifoliata species complex correspond to current island boundaries and specialized host plants. Main conclusions The temporally calibrated phylogeny of P. bifoliata represents the first invertebrate study to support the hypothesis that Miocene–Pliocene geological events and consequent cross‐island dispersal were pivotal promoters of species diversity in the Philippines. We hypothesize that ecological adaptation to specialized host plants, together with either local selection or genetic drift through within‐island allopatric isolation, present a plausible in situ speciation mechanism for the origin of these herbivorous insects.

Production of Homozygous Transgenic Rainbow Trout with Enhanced Disease Resistance - Pinwen Peter Chiou; Maria J. Chen; Chun-Mean Lin; Jenny Khoo; Jon Larson; Rich Holt; Jo-Ann Leong; Gary Thorgarrd; Thomas T. Chen (Marine Biotechnology, 2014)

Peptides Regulate Expression of Signaling Molecules in Kidney Cell Cultures during In Vitro Aging - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; A. O. Durnova; T. E. Nichik; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2014)

Genome characterization of sugarcane yellow leaf virus from China reveals a novel recombinant genotype - Yi-Hua Lin; San-Ji Gao; Mona B. Damaj; Hua-Ying Fu; Ru-Kai Chen; T. Erik Mirkov (Archives of Virology, 2014)

Modulation of the fluorescence yield in heliobacterial cells by induction of charge recombination in the photosynthetic reaction center - Kevin E. Redding; Iosifina Sarrou; Fabrice Rappaport; Stefano Santabarbara; Su Lin; Kiera T. Reifschneider (Photosynthesis Research, 2014)

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

An ecological function and services approach to total maximum daily load (TMDL) prioritization - Robert K. Hall; David Guiliano; Sherman Swanson; Michael J. Philbin; John Lin; Joan L. Aron; Robin J. Schafer; Daniel T. Heggem (Environmental Monitoring and Assessment, 2014)

Using the VIKOR method to evaluate the design of a water quality monitoring network in a watershed - C.-L. Chang; Y.-T. Lin (International Journal of Environmental Science and Technology, 2014)

Fatty Acid Methyl Esters and Solutol HS 15 Confer Neuroprotection after Focal and Global Cerebral Ischemia - Hung Wen Lin; Isabel Saul; Victoria L. Gresia; Jake T. Neumann; Kunjan R. Dave; Miguel A. Perez-Pinzon (Translational Stroke Research, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Cardiac glutaminolysis: a maladaptive cancer metabolism pathway in the right ventricle in pulmonary hypertension - Lin Piao; Yong-Hu Fang; Kishan Parikh; John J. Ryan; Peter T. Toth; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Volatile halocarbon emissions by three tropical brown seaweeds under different irradiances - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Emma C. Leedham; Claire Hughes; Andrew D. Robinson; Neil R. P. Harris; John A. Pyle; William T. Sturges (Journal of Applied Phycology, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Pushover analysis of reinforced concrete frames considering shear failure at beam-column joints - Y. C. Sung; T. K. Lin; C. C. Hsiao; M. C. Lai (Earthquake Engineering and Engineering Vibration, 2013)

Molecular mapping of two genes conferring resistance to Phytophthora sojae in a soybean landrace PI 567139B - Feng Lin; Meixia Zhao; Jieqing Ping; Austin Johnson; Biao Zhang; T. Scott Abney; Teresa J. Hughes; Jianxin Ma (Theoretical and Applied Genetics, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Effectiveness of participatory training for prevention of musculoskeletal disorders: a randomized controlled trial - Wenzhou Yu; Ignatius T. S. Yu; Xiaorong Wang; Zhimin Li; Sabrina Wan; Hong Qiu; Hui Lin; Shaohua Xie; Trevor Sun (International Archives of Occupational and Environmental Health, 2013)

Computer Aided Alignment and Quantitative 4D Structural Plasticity Analysis of Neurons - Ping-Chang Lee; Hai-yan He; Chih-Yang Lin; Yu-Tai Ching; Hollis T. Cline (Neuroinformatics, 2013)

FOXO1-mediated upregulation of pyruvate dehydrogenase kinase-4 (PDK4) decreases glucose oxidation and impairs right ventricular function in pulmonary hypertension: therapeutic benefits of dichloroacetate - Lin Piao; Vaninder K. Sidhu; Yong-Hu Fang; John J. Ryan; Kishan S. Parikh; Zhigang Hong; Peter T. Toth; Erik Morrow; Shelby Kutty; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2013)

Reliability of Postmortem Fentanyl Concentrations in Determining the Cause of Death - James R. Gill; Peter T. Lin; Lewis Nelson (Journal of Medical Toxicology, 2013)

Erratum to: Adsorption of arsenic(V) by iron-oxide-coated diatomite (IOCD) - Yi-Fong Pan; Cary T. Chiou; Tsair-Fuh Lin (Environmental Science and Pollution Research, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Climate trends in indices for temperature and precipitation across New York State, 1948–2008 - T. Z. Insaf; S. Lin; S. C. Sheridan (Air Quality, Atmosphere & Health, 2013)

Selenoprotein P and Yunnan Endemic Sudden Cardiac Death—an Ecological Study - Q. Li; X. Z. Li; T. Wang; L. W. Zhou; H. Q. Feng; L. Gao; J. R. Pei; C. Lin; C. X. Jiang (Biological Trace Element Research, 2013)

Molecular characterization and phylogenetic analysis of Sugarcane yellow leaf virus isolates from China - San-Ji Gao; Yi-Hua Lin; Yong-Bao Pan; Mona B. Damaj; Qin-Nan Wang; T. Erik Mirkov; Ru-Kai Chen (Virus Genes, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Equal modulation of endothelial cell function by four distinct tissue-specific mesenchymal stem cells - Ruei-Zeng Lin; Rafael Moreno-Luna; Bin Zhou; William T. Pu; Juan M. Melero-Martin (Angiogenesis, 2012)

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Mortality in a Chinese chrysotile miner cohort - Xiaorong Wang; Sihao Lin; Eiji Yano; Hong Qiu; Igtanius T. S. Yu; Lapah Tse; Yajia Lan; Mianzhen Wang (International Archives of Occupational and Environmental Health, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Climate Change Effects on Hydrology and Ecology of Wetlands in the Mid-Atlantic Highlands - Jonathan L. Pitchford; Chenjie Wu; LianShin Lin; J. Todd Petty; Richard Thomas; Walter E. Veselka; Danny Welsch; Nicolas Zegre; James T. Anderson (Wetlands, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Characteristics of Polycyclic Aromatic Hydrocarbon Emissions of Particles of Various Sizes from Smoldering Incense - T. T. Yang; T. S. Lin; J. J. Wu; F. J. Jhuang (Bulletin of Environmental Contamination and Toxicology, 2012)

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle - Yong-Hu Fang; Lin Piao; Zhigang Hong; Peter T. Toth; Glenn Marsboom; Peter Bache-Wiig; Jalees Rehman; Stephen L. Archer (Journal of Molecular Medicine, 2012)

Late Triassic bivalves associated with a hydrothermal vent system in the Yidun Island Arc (SW China) of the eastern Tethys - Li Lin; LiDong Zhu; YanChun Pang; JinGeng Sha; Franz T. Fürsich; XiuGen Fu; XinLi Wang (Science China Earth Sciences, 2011)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Correlating recurrent radon precursors with local earthquake magnitude and crust strain near the Chihshang fault of eastern Taiwan - T. Kuo; C. Lin; C. Su; C. Liu; C. H. Lin; C. Chang; C. Chiang (Natural Hazards, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Kinetic migration of isothiazolinone biocides from paper packaging to Tenax and Porapak - Q.-B. Lin; T.-J. Wang; H. Song; R.-Z. Wang (Food Additives & Contaminants: Part A, 2011)

A multivalent vaccine for type 1 diabetes skews T cell subsets to Th2 phenotype in NOD mice - Ming S. Lin; Hubert M. Tse; Meghan M. Delmastro; Suzanne Bertera; Caterina T. Wong; Robert Lakomy; Jing He; Martha M. Sklavos; Gina M. Coudriet; Massimo Pietropaolo; Massimo M. Trucco; Jon D. Piganelli (Immunologic Research, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Papillary thyroid cancer incidence rates vary significantly by birthplace in Asian American women - Pamela L. Horn-Ross; Laura A. McClure; Ellen T. Chang; Christina A. Clarke; Theresa H. M. Keegan; Rudolph P. Rull; Thu Quach; Scarlett Lin Gomez (Cancer Causes & Control, 2011)

Chronic exposure to ambient particulate matter alters cardiac gene expression patterns and markers of oxidative stress in rats - Boris Z. Simkhovich; Michael T. Kleinman; Ruty Mehrian-Shai; Ya-Hsuan Hsu; Dianne Meacher; Glenn Gookin; Michael Mac Kinnon; Karina Salazar; Paul Willet; Gang Feng; Simon M. Lin; Robert A. Kloner (Air Quality, Atmosphere & Health, 2011)

An engineering intervention resulting in improvement in lung function and change in urinary 8-hydroxydeoxyguanosine among foundry workers in Taiwan - Ming-Hsiu Lin; Saou-Hsing Liou; Ching-Wen Chang; I-Hsiao Huang; Paul T. Strickland; Ching-Huang Lai (International Archives of Occupational and Environmental Health, 2011)

Algal Growth Control Within Natural Water Purification Systems: Macrophyte Light Shading Effects - T. Y. Yeh; T. Y. Ke; Y. L. Lin (Water, Air, & Soil Pollution, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

Analysis of isothiazolinone biocides in paper for food packaging by ultra-high-performance liquid chromatography–tandem mass spectrometry - Q.-B. Lin; T.-J. Wang; H. Song; B. Li (Food Additives & Contaminants: Part A, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Adsorption of arsenic(V) by iron-oxide-coated diatomite (IOCD) - Yi-Fong Pan; Cary T. Chiou; Tsair-Fuh Lin (Environmental Science and Pollution Research, 2010)

Trace metal cycling in the surface water of the South China Sea: Vertical fluxes, composition, and sources - Tung-Yuan Ho; Wen-Chen Chou; Ching-Ling Wei; Fei-Jan Lin; George T. F. Wong; Hui-Ling Line (Limnology and Oceanography, 2010)
We deployed floating traps in the surface waters of the South China Sea on four occasions at depths of 30 m, 100 m, and 160 m from 2006 to 2007 to quantify vertical metal fluxes in the surface water and examine trace metal composition in the sinking particles to investigate their sources. The elements determined include 13 trace metals and 8 major elements. The fluxes for most of the bioactive elements at 30 m varied markedly during different seasons and strongly co‐varied with organic matter production, but the fluxes at 160 m were low and consistent under different seasons, showing that most of the elements were internally recycled in the surface water during productive seasons. Most of the bioactive trace metals in sinking particles were correlated with biogenic P, and their P‐normalized quotas were also strongly associated with lithogenic Al. The ratios of metals to Al and P for most of the bioactive trace metals were significantly higher than the ratios in lithogenic particles and than intracellular quotas in plankton, respectively, indicating that the trace metals in the sinking particles were abiogenic, nonlithogenic, and adsorbed on biogenic particles. The comparable fluxes between aeolian deposition and the sinking particles in the mixed layer demonstrate that the highly enriched trace metals in the sinking particles were attributed to input from anthropogenic aerosols. The coupling and transport of anthropogenic trace metals with biogenic particles in oceanic surface waters may be an important mechanism for trace metal cycling in global oceans.

Simultaneous declines in radon and methane precursory to 2008 M W 5.0 Antung earthquake: corroboration of in-situ volatilization - T. Kuo; W. Cheng; C. Lin; K. Fan; G. Chang; T. Yang (Natural Hazards, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Therapeutic HPV DNA vaccines - Ken Lin; Elena Roosinovich; Barbara Ma; Chien-Fu Hung; T.-C. Wu (Immunologic Research, 2010)

Dopaminergic neurotoxicity following pulmonary exposure to manganese-containing welding fumes - Krishnan Sriram; Gary X. Lin; Amy M. Jefferson; Jenny R. Roberts; Rebecca S. Chapman; Bean T. Chen; Joleen M. Soukup; Andrew J. Ghio; James M. Antonini (Archives of Toxicology, 2010)

Estimation of aseismic crustal-strain using radon precursors of the 2003 M 6.8, 2006 M 6.1, and 2008 M 5.0 earthquakes in eastern Taiwan - T. Kuo; C. Lin; G. Chang; K. Fan; W. Cheng; C. Lewis (Natural Hazards, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Epigenetic regulation of peanut allergen gene Ara h 3 in developing embryos - Guohua Fu; Yujuan Zhong; Chenlong Li; Yin Li; Xiaodong Lin; Bin Liao; Edward W. T. Tsang; Keqiang Wu; Shangzhi Huang (Planta, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Automated building change detection using UltraCamD images and existing CAD data - Zhen Liu; Peng Gong; Peijun Shi; Howu Chen; Lin Zhu; T. Sasagawa (International Journal of Remote Sensing, 2010)

Velocity structure and gas hydrate saturation estimation on active margin off SW Taiwan inferred from seismic tomography - Win-Bin Cheng; S. S. Lin; T. K. Wang; C. S. Lee; C. S. Liu (Marine Geophysical Research, 2010)

Response of benthic macroinvertebrate communities to highway construction in an Appalachian watershed - Lara B. Hedrick; Stuart A. Welsh; James T. Anderson; Lian-Shin Lin; Yushun Chen; Xinchao Wei (Hydrobiologia, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

The inhibition of pyruvate dehydrogenase kinase improves impaired cardiac function and electrical remodeling in two models of right ventricular hypertrophy: resuscitating the hibernating right ventricle - Lin Piao; Yong-Hu Fang; Virgilio J. J. Cadete; Christian Wietholt; Dalia Urboniene; Peter T. Toth; Glenn Marsboom; Hannah J. Zhang; Idith Haber; Jalees Rehman; Gary D. Lopaschuk; Stephen L. Archer (Journal of Molecular Medicine, 2010)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Spatio‐temporal variation in the elemental compositions of otoliths of southern bluefin tuna Thunnus maccoyii in the Indian Ocean and its ecological implication - C. H. Wang; Y. T. Lin; J. C. Shiao; C. F. You; W. N. Tzeng (Journal of Fish Biology, 2009)
The elements Na, Mg, Mn, Ca, Sr and Ba in otoliths of southern bluefin tuna Thunnus maccoyii , collected from their feeding ground in the central Indian Ocean and spawning ground between southern Java and north‐western Australia were measured by laser‐ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) and compared among sampling locations and developmental stages. The Na, Mg and Mn to Ca concentration ratios were significantly higher at the larval stage than at the adult stage, and the ratio reached a peak at the first inflection point of the otolith, mean ± s.d. 43·3 ± 4·9 days after hatching and decreased sharply to a low level thereafter. The temporal change of the elements:Ca ratios in the first inflection point corresponded to the life stage transition from larva to juvenile, indicating that the uptake rate of elements from ambient waters was significantly influenced by the ontogenetic change in the fish. The elemental composition at the otolith edge differed significantly in sub‐adults on the feeding grounds and adults on the spawning grounds. Thus, the otolith elemental composition can be used as a biological tracer to study the time of the ontogenetic shift and to reconstruct the past migratory environmental history of T. maccoyii . In addition, the elemental composition of the otolith core of the adult was similar between feeding and spawning grounds, indicating that the fish in the Indian Ocean had the same larval origin, which is consistent with the single spawning population hypothesis.

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Accumulation of H2O2 in xylem fluids of cucumber stems during ASM-induced systemic acquired resistance (SAR) involves increased LOX activity and transient accumulation of shikimic acid - T. -C. Lin; H. Ishii (European Journal of Plant Pathology, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Identification of soil heavy metal sources from anthropogenic activities and pollution assessment of Fuyang County, China - X. Y. Zhang; F. F. Lin; Mike T. F. Wong; X. L. Feng; K. Wang (Environmental Monitoring and Assessment, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Rotavirus infection increases the risk of bacteremia in children with nontyphoid Salmonella gastroenteritis - T.-Y. Hung; M.-C. Liu; C.-F. Hsu; Y.-C. Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The in vitro susceptibility of Campylobacter spp. to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Raman spectroscopic study of K-lingunite at various pressures and temperatures - Lin-gun Liu; C.-C. Lin; Y. J. Yung; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Contrasting patterns of morphological and neutral genetic divergence among geographically proximate populations of sockeye salmon Oncorhynchus nerka in Lake Aleknagik, Alaska - J. Lin; E. Ziegler; T. P. Quinn; L. Hauser (Journal of Fish Biology, 2008)
Levels of differentiation in morphological traits (age at maturity, body length at age, egg mass and body depth) and spawning time were examined in sockeye salmon Oncorhynchus nerka from three geographically proximate but physically distinct creeks in Lake Aleknagik, Alaska. Happy Creek fish had significantly greater values for most measured morphological traits, and Eagle Creek fish spawned significantly later than fish in the other creeks. Phenotypic differentiation between creeks, measured as P ST , was then compared with microsatellite marker differentiation between creeks, measured as F ST . No correlations were apparent between P ST and F ST values, and P ST values were generally significantly larger than zero ( P ST = 0·0018–0·31) whereas F ST values were not ( F ST =−0·0004 to 0·0016). The insignificant pair‐wise F ST values between creek samples indicated that gene flow occurs between creeks, assuming the creek populations have reached migration–drift equilibrium. However, the strong homing behaviour of sockeye salmon precludes a scenario in which fish from the three creeks constitute a single population that segregates by body size. Rather, significant phenotypic differentiation suggests that strong divergent selection occurs on the phenotypic traits despite the homogenizing effects of gene flow.

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent - DIANA H. WALL; MARK A. BRADFORD; MARK G. ST. JOHN; JOHN A. TROFYMOW; VALERIE BEHAN‐PELLETIER; DAVID E. BIGNELL; J. MARK DANGERFIELD; WILLIAM J. PARTON; JOSEF RUSEK; WINFRIED VOIGT; VOLKMAR WOLTERS; HOLLEY ZADEH GARDEL; et al. (Global Change Biology, 2008)
Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the difficulties of manipulating invertebrate animals experimentally across large geographic gradients. This is compounded by deficient or inconsistent taxonomy. We report a global decomposition experiment to assess the importance of soil animals in C mineralization, in which a common grass litter substrate was exposed to natural decomposition in either control or reduced animal treatments across 30 sites distributed from 43°S to 68°N on six continents. Animals in the mesofaunal size range were recovered from the litter by Tullgren extraction and identified to common specifications, mostly at the ordinal level. The design of the trials enabled faunal contribution to be evaluated against abiotic parameters between sites. Soil animals increase decomposition rates in temperate and wet tropical climates, but have neutral effects where temperature or moisture constrain biological activity. Our findings highlight that faunal influences on decomposition are dependent on prevailing climatic conditions. We conclude that (1) inclusion of soil animals will improve the predictive capabilities of region‐ or biome‐scale decomposition models, (2) soil animal influences on decomposition are important at the regional scale when attempting to predict global change scenarios, and (3) the statistical relationship between decomposition rates and climate, at the global scale, is robust against changes in soil faunal abundance and diversity.

Deaths from non-melanoma skin cancer in Western Australia - J. Girschik; Lin Fritschi; T. Threlfall; T. Slevin (Cancer Causes & Control, 2008)

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Residential proximity to large airports and potential health impacts in New York State - S. Lin; J. P. Munsie; M. Herdt-Losavio; S. A. Hwang; K. Civerolo; K. McGarry; T. Gentile (International Archives of Occupational and Environmental Health, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Determination of Particulate-Bound Formaldehyde from Burning Incense by Solid Phase Microextraction - S. W. Liou; C. Y. Chen; T. T. Yang; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2008)

Spatiotemporal dynamics of bacterial populations in the anoxic Cariaco Basin - Xueju Lin; Mary I. Scranton; Andrei Y. Chistoserdov; Ramon Varela; Gordon T. Taylor (Limnology and Oceanography, 2008)
Distributions of bacterial populations in the anoxic Cariaco Basin were studied over 2 yr (five cruises) at three stations using fluorescence in situ hybridization (FISH) and terminal restriction fragment length polymorphism (T‐RFLP) of 16S ribosomal ribonucleic acid (rRNA) genes. FISH results demonstrate that the contribution of ɛ‐proteobacterial abundances to total prokaryotic inventories was relatively constant among cruises, and this group was dominant in the redoxcline, accounting for 18% of DAPI (4'6‐diamidino‐2‐phenylindole)‐stained counts on average. In contrast, β‐proteobacteria were more variable. Sulfate reducers, α‐, and γ‐proteobacteria accounted for minor components of the anaerobic microbial communities. T‐RFLP fingerprinting also showed significant temporal shifts in bacterial community composition. The greatest variations in bacterial community structure were evident among oxic, transitional, and anoxic zones, but significant horizontal variations were also evident within redoxclines of three different stations. A statistical analysis of T‐RFLP patterns revealed clear spatiotemporal patterns in bacterial community structure along the redox gradient among sites and over time. Total prokaryotic abundances corresponded well with seasonal variations in organic carbon fluxes above the redoxcline. However, no single measured environmental variable (O 2 , H 2 S, S 2 O 3 2‐ , H 4 SiO 4 , NO 3 − , PO 4 3‐ , microbial biomass, chemoautotrophic production) explained the temporal oscillations of the dominant bacterial groups. Analyses suggest that redox gradients, terrestrial inputs, and disturbance due to lateral intrusions of adjacent waters could significantly affect bacterial community composition in the Cariaco Basin.

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Culture Duration Modulates Collagen Hydrolysate-Induced Tissue Remodeling in Chondrocyte-Seeded Agarose Hydrogels - Kenneth W. Ng; Justin D. Saliman; Evan Y. Lin; Lauren Y. Statman; Lindsay E. Kugler; Sean B. Lo; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2007)

Dissipation of Pendimethalin in the Garlic (Allium sativum L.) under Subtropical Condition - H. T. Lin; S. W. Chen; C. J. Shen; C. Chu (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Characteristics of Emissions of Volatile Organic Compounds from Smoldering Incense - T. T. Yang; T. S. Lin; M. Chang (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

A brief summary of Dr. G. V. Rao’s research interests - Yeong-Jer Lin; James T. Moore; Jack Fishman (Natural Hazards, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Cytotoxic kurubasch aldehyde from Trichilia emetica - Maminata Traore; Lin Zhai; Ming Chen; Carl Erik Olsen; Nacoulma Odile; Guissou I. Pierre; Ouédrago J. Bosco; Guigemdé T. Robert; S. Brøgger Christensen (Natural Product Research, 2007)

Responses of Metapopulation Dynamics to Two Different Kinds of Habitat Destruction Caused by Human Activities - H. Y. Liu; Z. S. Lin; T. Wen (Plant Ecology, 2006)

Characterization of Gas and Particle Emission from Smoldering Incenses with Various Diameters - T. T. Yang; C. C. Chen; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Multifunctionality of paddy fields in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan (Paddy and Water Environment, 2006)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Serum Heat Shock Protein (HSP70) and Its Antibody (Anti-HSP70) Levels in Male Foundry Workers in Taiwan - C.-J. Chen; H.-J. Wen; S.-H. Liu; M.-S. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Soil hydraulic manipulation and organic amendment for the enhancement of selenium volatilization in a soil–pickleweed system - B. Shrestha; S. Lipe; K. A. Johnson; T. Q. Zhang; W. Retzlaff; Z.-Q. Lin (Plant and Soil, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Copper‐dependent iron transport in coastal and oceanic diatoms - Maria T. Maldonado; Andrew E. Allen; Joanne S. Chong; Kevin Lin; Dan Leus; Nataliya Karpenko; Shannon L. Harris (Limnology and Oceanography, 2006)
We investigated the presence of plasmalemma‐bound copper‐containing oxidases associated with the inducible iron (Fe) transport system in two diatoms of the genus Thalassiosira . Under Fe‐limiting conditions, Thalassiosira oceanica , an oceanic isolate, was able to enzymatically oxidize inorganic Fe(II) extracellularly. This oxidase activity was dependent on copper (Cu) availability and diminished by exposure to a multi‐Cu oxidase (MCO) inhibitor. The rates of Fe uptake from ferrioxamine B by Fe‐limited T. oceanica were also dependent on Cu availability in the growth media. The effects of Cu limitation on Fe(II) oxidation and Fe uptake from ferrioxamine B were partially reversed after a short exposure to a Cu addition, indicating that the putative oxidases contain Cu. Limited physiological experiments were also performed with the coastal diatom Thalassiosira pseudonana and provided some evidence for putative Cu‐containing oxidases in the high‐affinity Fe transport system of this isolate. To support these preliminary physiological data, we searched the newly available T. pseudonan a genome for a multi‐Cu‐containing oxidase gene and, using real‐time polymerase chain reaction (PCR), quantified its expression under various Fe and Cu levels. We identified a putative MCO gene with predicted transmembrane domains and found that transcription levels of this gene were significantly elevated in Fe‐limited cells relative to Fe‐replete cells. These data collectively suggest that putative MCOs are part of the inducible Fe transport system of Fe‐limited diatoms, which act to oxidize Fe(II) following reductive dissociation of Fe(III) from strong organic complexes.

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Enhanced Protein Delivery from Photopolymerized Hydrogels Using a Pseudospecific Metal Chelating Ligand - Chien-Chi Lin; Andrew T. Metters (Pharmaceutical Research, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Stable RNA Interference in Spodoptera frugiperda Cells by a DNA Vector-based Method - Chih-Chien Lin; John T. -A. Hsu; Kai-Ling Huang; Hung-Kuan Tang; Yiu-Kay Lai (Biotechnology Letters, 2006)

Primate-Specific Endogenous Cis-Antisense Transcription in the Human 5q31 Protocadherin Gene Cluster - Leonard Lipovich; Ravi Raj Vanisri; Say Li Kong; Chin-Yo Lin; Edison T. Liu (Journal of Molecular Evolution, 2006)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Potential Exposure to VOCs Caused by Dry Process Photocopiers: Results From a Chamber Study - D.-J. Hsu; H.-L. Huang; C.-H. Chien; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

Infectious bursal disease virus recovery from Vero cells transfected with RNA transcripts is enhanced by expression of the structural proteins in trans - M. A. Peters; T. L. Lin; C. C. Wu (Archives of Virology, 2005)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Evaluation of Candidate Gene Effects for Beef Backfat via Bayesian Model Selection - Xiao-Lin Wu; Michael D. MacNeil; Sachinadan De; Qian-Jun Xiao; Jennifer J. Michal; Charles T. Gaskins; Jerry J. Reeves; Jan R. Busboom; Raymond W. Wright; Zhihua Jiang (Genetica, 2005)

Acute Toxicity of Thallium to Daphnia magna and Ceriodaphnia dubia - T.-S. Lin; P. Meier; J. Nriagu (Bulletin of Environmental Contamination and Toxicology, 2005)

Characterization of Mesenchyme Homeobox 2 (MEOX2) transcription factor binding to RING finger protein 10 - Jijin Lin; Mona T. Friesen; Patricia Bocangel; David Cheung; Kathy Rawszer; Jeffrey T. Wigle (Molecular and Cellular Biochemistry, 2005)

Thallium in Whole Blood Samples from College Students in Taiwan - T.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 2: Hydrostatic mesoscale numerical simulations of supergradient wind flow and streamwise ageostrophic frontogenesis - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. D. Cetola; J. J. Charney; A. J. Riordan; Y.-L. Lin; K. T. Waight (Meteorology and Atmospheric Physics, 2005)

Automatic optimum order selection of parametric modelling for the evaluation of abnormal intra-QRS signals in signal-averaged electrocardiograms - C. -C. Lin; C. -M. Chen; I. -F. Yang; T. -F. Yang (Medical & Biological Engineering & Computing, 2005)

Effect of Air Flow on Emission of Smoldering Incense - T. T. Yang; C. C. Chen; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2005)

Histology and histochemical enzyme‐staining patterns of major immune organs in Epinephelus malabaricus - H.‐T. Lin; H.‐Y. Lin; H.‐L. Yang (Journal of Fish Biology, 2005)
The histological architecture of major immune organs in the Malabar grouper Epinephelus malabaricus was investigated. The novel characteristics such as melanomacrophage centres (MMCs) appeared in the thymus and lymphopoietic tissue formed as foci in the head kidney. Leukocyte distribution in organs was identified by enzyme histochemistry. β‐glucuronidase (BG) reactive cells in the cortex region of the thymus were botryoidally aggregated. Both acid phosphatase (AcP) and BG reactive cells concentrated within the specialized lymphopoietic foci in the head kidney, suggesting that the foci might be functional. Primitive histological characters of immunity were observed in the spleen. Although leukocyte aggregation was demonstrated in the spleen, additional enzyme histochemistry indicated that the aggregate might not be the equivalent of white pulp found in other vertebrates. The histological evidence did not support intestinal involvement in the immune system: there was no demonstrable gut associated lymphoid tissue. The limited distribution in the cortex and medulla boundary and the condensed format of the lymphocytes suggests a functional role for the MMC in the thymus of E. malabaricus . The MMC appearance in the thymus of a teleost was unusual.

Trace Elements in Cultured Tilapia (Oreochromis mossambicus): Results from a Farm in Southern Taiwan - T.-S. Lin; C.-S. Lin; C.-L. Chang (Bulletin of Environmental Contamination and Toxicology, 2005)

Trace Metals in Mosquito Coil Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2005)

Infectious bursal disease virus polyprotein expression arrests growth and mitogenic stimulation of B lymphocytes - M. A. Peters; T. L. Lin; C. C. Wu (Archives of Virology, 2004)

Whole Blood Vanadium in Taiwanese College Students - T.-S. Lin; C.-L. Chang; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2004)

Molecular diversity of methanotrophs in Transbaikal soda lake sediments and identification of potentially active populations by stable isotope probing - Ju‐Ling Lin; Stefan Radajewski; Bulat T. Eshinimaev; Yuri A. Trotsenko; Ian R. McDonald; J Colin Murrell (Environmental Microbiology, 2004)
Summary Soda lakes are an environment with an unusually high pH and often high salinity. To identify the active methanotrophs in the Soda lake sediments, sediment slurries were incubated with a 10% (v/v) 13 CH 4 headspace and the 13 C‐labelled DNA was subsequently extracted from these sediments following CsCl density gradient centrifugation. This DNA was then used as a template for PCR amplification of 16S rRNA genes and genes encoding PmoA and MmoX of methane monooxygenase, key enzymes in the methane oxidation pathway. Phylogenetic analysis of 16S rRNA genes, PmoA and MmoX identified that strains of Methylomicrobium , Methylobacter , Methylomonas and ‘Methylothermus’ had assimilated the 13 CH 4 . Phylogenetic analysis of PmoA sequences amplified from DNA extracted from Soda lake sediments before Stable Isotope Probing (SIP) treatment showed that a much wider diversity of both type I and type II methanotroph sequences are present in this alkaline environment. The majority of methanotroph sequences detected in the 13 C‐DNA studies were from type I methanotrophs, with 50% of 16S rRNA clones and 100% of pmoA clones from both Lake Suduntuiskii Torom and Lake Gorbunka suggesting that the type I methanotrophs are probably responsible for the majority of methane oxidation in this environment.

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

Mycobacterium Reverse Hybridization Line-Probe Assay Used to Diagnose Disseminated Mycobacterium haemophilum Infection in a Child with Acute Lymphoblastic Leukemia - F. Bosma; J. M. Deckers-Kocken; S. S. N. de Graaf; T. Schlin; W. J. G. Melchers; J. A. Hoogkamp-Korstanje (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Elevated Exposure to Nitrogen Dioxide During Food Preparation: Results from a Cooking Laboratory - T.-S. Lin; Y.-L. Huang (Bulletin of Environmental Contamination and Toxicology, 2004)

A likelihood approach for mapping growth trajectories using dominant markers in a phase-unknown full-sib family - C.-X. Ma; M. Lin; R. C. Littell; T. Yin; R. Wu (Theoretical and Applied Genetics, 2004)

Fine linkage mapping enables dissection of closely linked quantitative trait loci for seed dormancy and heading in rice - Y. Takeuchi; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Evidence for the existence of some dissociation in an otherwise strong linkage disequilibrium between mitochondrial and chloroplastic genomes in Cyclobalanopsis glauca - T.‐P. Lin; W.‐J. Chuang; S. S. F. Huang; S.‐Y. Hwang (Molecular Ecology, 2003)
Variations in mitochondrial DNA in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. were studied in 140 trees from 32 populations collected from within the tree's natural range. By sequencing two mitochondrial DNA intron fragments ( nad 4/3 ‐nad 4/4r and nad 7/2 ‐nad 7/3r), we revealed a total of 1788 bp and five polymorphic sites which allowed us to distinguish six mitotypes. The mitochondrial DNA markers provided replicated data to support population phylogeographical scenarios suggested previously using chloroplastic DNA markers. The gene genealogical tree of mitochondrial DNA was partially congruent with the chloroplastic DNA tree owing to the slower mutation rate and different mutational direction. Significant linkage disequilibrium existed between the two organellar genomes. Further paring analyses between fragments synthesized using different primers, accompanied by exclusion of polymorphic sites, showed that the random association could be attributed specifically to one of the polymorphic sites of the pet G‐ trn P fragment of the chloroplastic genome, and the three polymorphic sites of the nad 4/3‐ nad 4/4r fragment of the mitochondrial genome. The former was inferred to derive from paternal leakage, and the latter from recurrent mutation. These polymorphic sites were also responsible for uncoupling of the combined gene tree of mitotype and chlorotype. In conclusion, specific fragments found in this study contribute to the incomplete congruence of the two organellar lineages that otherwise associate well phylogeographically.

A mixture model approach to detecting differentially expressed genes with microarray data - Chap T. Le; Wei Pan; Jizhen Lin (Functional & Integrative Genomics, 2003)

Tropical Glacier and Ice Core Evidence of Climate Change on Annual to Millennial Time Scales - Lonnie G. Thompson; Ellen Mosley-Thompson; M. E. Davis; P.-N. Lin; K. Henderson; T. A. Mashiotta (Climatic Change, 2003)

Trace Metals in Chinese Joss Stick Smoke - T.-S. Lin; F.-M. Shen (Bulletin of Environmental Contamination and Toxicology, 2003)

A method for inflorescence proliferation - C.-S. Lin; C.-T. Chen; C.-C. Lin; W.-C. Chang (Plant Cell Reports, 2003)

Carbon sequestration in arid‐land forest - J. M. GRÜNZWEIG; T. LIN; E. ROTENBERG; A. SCHWARTZ; D. YAKIR (Global Change Biology, 2003)
Rising atmospheric CO 2 concentrations may lead to increased water availability because the water use efficiency of photosynthesis (WUE) increases with CO 2 in most plant species. This should allow the extension of afforestation activities into drier regions. Using eddy flux, physiological and inventory measurements we provide the first quantitative information on such potential from a 35‐year old afforestation system of Aleppo pine ( Pinus halepensis Mill.) at the edge of the Negev desert. This 2800 ha arid‐land forest contains 6.5 ± 1.2 kg C m −2 , and continues to accumulate 0.13–0.24 kg C m −2 yr −1 . The CO 2 uptake is highest during the winter, out of phase with most northern hemispheric forest activity. This seasonal offset offers low latitude forests ∼10 ppm higher CO 2 concentrations than that available to higher latitude forests during the productive season, in addition to the 30% increase in mean atmospheric CO 2 concentrations since the 1850s. Expanding afforestation efforts into drier regions may be significant for C sequestration and associated benefits (restoration of degraded land, reducing runoff, erosion and soil compaction, improving wildlife) because of the large spatial scale of the regions potentially involved (ca. 2 × 10 9 ha of global shrub‐land and C4 grassland). Quantitative information on forest activities under dry conditions may also become relevant to regions predicted to undergo increasing aridity.

Trace Metals in Candle Smoke - T.-S. Lin; F.-M. Shen; J.-L. Chen; M.-H. Yang (Bulletin of Environmental Contamination and Toxicology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Adsorption of Copper in the Different Sorbent/Water Ratios of Soil Systems - T. W. Chang; M. K. Wang; C. Lin (Water, Air, & Soil Pollution, 2002)

Mapping quantitative trait loci controlling seed longevity in rice (Oryza sativa L.) - K. Miura; S. Lin; M. Yano; T. Nagamine (Theoretical and Applied Genetics, 2002)

Genetic dissection of a genomic region for a quantitative trait locus, Hd3, into two loci, Hd3a and Hd3b, controlling heading date in rice - L. Monna; H. Lin; S. Kojima; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2002)

Raman spectra of hydrous γ -Mg 2 SiO 4 at various pressures and temperatures - L. Liu; C.-C. Lin; T. P. Mernagh; T. Inoue (Physics and Chemistry of Minerals, 2002)

Evolutionary and taxonomic implications of conserved structural motifs between picornaviruses and insect picorna-like viruses - L. Liljas; J. Tate; T. Lin; P. Christian; J. E. Johnson (Archives of Virology, 2002)

Thallium Concentration in Lake Trout from Lake Michigan - T.-S. Lin; J. Nriagu; X.-Q. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Plasmids carrying cloned fragments of RF DNA from the filamentous phage φLf can be integrated into the host chromosome via site-specific integration and homologous recombination - N.-T. Lin; R.-Y. Chang; S.-J. Lee; Y.-H. Tseng (Molecular Genetics and Genomics, 2001)

Cultures of equine respiratory epithelial cells and organ explants as tools for the study of equine influenza virus infection - C. Lin; R. E. Holland Jr; N. M. Williams; T. M. Chambers (Archives of Virology, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Environmental Exposure to Polycyclic Aromatic Hydrocarbons and Total Suspended Particulates in a Taiwanese Temple - T-C. Lin; F-H. Chang; J-H. Hsieh; H-R. Chao; M-R. Chao (Bulletin of Environmental Contamination and Toxicology, 2001)

( R )-Methanandamide and Δ 9 -THC as discriminative stimuli in rats: tests with the cannabinoid antagonist SR-141716 and the endogenous ligand anandamide - Järbe T.; Lamb R.; Lin S.; Makriyannis A. (Psychopharmacology, 2001)

A natural-gradient field tracer test for evaluation of pollutant-transport parameters in a porous-medium aquifer - Y. Yang; X. Lin; T. Elliot; R. Kalin (Hydrogeology Journal, 2001)

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Genetic transformation of duckweed Lemna gibba and Lemna minor - Yuri T. Yamamoto; Nirmala Rajbhandari; Xiaohong Lin; Ben A. Bergmann; Yufuko Nishimura; Anne-Marie Stomp (In Vitro Cellular & Developmental Biology - Plant, 2001)

Characterization of a SINE species from vicuna and its distribution in animal species including the family Camelidae - Z. Lin; O. Nomura; T. Hayashi; Y. Wada; Hiroshi Yasue (Mammalian Genome, 2001)

Allozyme variations in Michelia formosana (Kanehira) Masamune(Magnoliaceae), and the inference of a glacial refugium in Taiwan - T.-P. Lin (Theoretical and Applied Genetics, 2001)

Time-dependent responses of soil CO2 efflux components to elevated atmospheric [CO2] and temperature in experimental forest mesocosms - Guanghui Lin; Paul T. Rygiewicz; James R. Ehleringer; Mark G. Johnson; David T. Tingey (Plant and Soil, 2001)

Functional Asymmetry of the Sodium- d -Glucose Cotransporter Expressed in Yeast Secretory Vesicles - M.A. Firnges; J.-T. Lin; R.K.-H. Kinne (The Journal of Membrane Biology, 2001)

Surveys of Volatile Organic Compounds in Soil and Groundwater at Industrial Sites in Taiwan - M.-C. T. Kuo, C.-M. Chen, C. H. Lin, H. C (Bulletin of Environmental Contamination and Toxicology, 2000)

Characterization and detection of epistatic interactions of 3 QTLs, Hd1, Hd2, and Hd3, controlling heading date in rice using nearly isogenic lines - H. X. Lin; T. Yamamoto; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2000)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

S1 analysis of long PCR heteroduplexes: detection of chloroplast indel polymorphisms in Fragaria - J. Lin; T. M. Davis (Theoretical and Applied Genetics, 2000)

Raman spectroscopic study of hydroxyl-clinohumite at various pressures and temperatures - C.-C. Lin; L.-G. Liu; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2000)

Mineralization of organic sulfur and its importance as a reservoir of plant-available sulfur in upland soils of north China - W. Zhou; S. T. Li; H. Wang; P. He; B. Lin (Biology and Fertility of Soils, 1999)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

Probing Transmembrane Topology of the High-Affinity Sodium/Glucose Cotransporter (SGLT1) with Histidine-Tagged Mutants - J.-T. Lin; J. Kormanec; D. Homerová; R.K.-H. Kinne (The Journal of Membrane Biology, 1999)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, , C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Mitochondrion‐rich cells in the embryonic yolk sac of Oreochromis mossambicus - H. C. Lin; P. P. Hwang; T. H. Lee (Journal of Fish Biology, 1999)
By removing a small amount of yolk, tilapia embryos were dechorionated successfully as early as 30 h after fertilization. Using DASPEI, a mitochondrion‐specific fluorescent stain, we were able to determine the first appearance of the mitochondrion rich cells on the surface of the yolk sac 26 h after fertilization ( c. 2 h after the beginning of gastrula stage). However, with scanning electron microscopy examination, no apical crypt could be found until 48 h after fertilization.

High-pressure Raman spectroscopic study of chondrodite - C.-C. Lin; L.-g. Liu; T. Irifune (Physics and Chemistry of Minerals, 1999)

Elevated CO 2 and temperature impacts on different components of soil CO 2 efflux in Douglas‐fir terracosms - Guanghui Lin; James R. Ehleringer; PauL. T. Rygiewicz; Mark G. Johnson; David T. Tingey (Global Change Biology, 1999)
Although numerous studies indicate that increasing atmospheric CO 2 or temperature stimulate soil CO 2 efflux, few data are available on the responses of three major components of soil respiration [i.e. rhizosphere respiration (root and root exudates), litter decomposition, and oxidation of soil organic matter] to different CO 2 and temperature conditions. In this study, we applied a dual stable isotope approach to investigate the impact of elevated CO 2 and elevated temperature on these components of soil CO 2 efflux in Douglas‐fir terracosms. We measured both soil CO 2 efflux rates and the 13 C and 18 O isotopic compositions of soil CO 2 efflux in 12 sun‐lit and environmentally controlled terracosms with 4‐year‐old Douglas fir seedlings and reconstructed forest soils under two CO 2 concentrations (ambient and 200 ppmv above ambient) and two air temperature regimes (ambient and 4 °C above ambient). The stable isotope data were used to estimate the relative contributions of different components to the overall soil CO 2 efflux. In most cases, litter decomposition was the dominant component of soil CO 2 efflux in this system, followed by rhizosphere respiration and soil organic matter oxidation. Both elevated atmospheric CO 2 concentration and elevated temperature stimulated rhizosphere respiration and litter decomposition. The oxidation of soil organic matter was stimulated only by increasing temperature. Release of newly fixed carbon as root respiration was the most responsive to elevated CO 2 , while soil organic matter decomposition was most responsive to increasing temperature. Although some assumptions associated with this new method need to be further validated, application of this dual‐isotope approach can provide new insights into the responses of soil carbon dynamics in forest ecosystems to future climate changes.

Δ 9 -THC training dose as a determinant for ( R )-methanandamide generalization in rats - T. U. C. Järbe; R. J. Lamb; A. Makriyannis; S. Lin; A. Goutopoulos (Psychopharmacology, 1998)

Localizations of NS3 and E proteins in mouse brain infected with mutant strain of Japanese encephalitis virus - J. J. Wang; C. L. Liao; C. I. Yang; Y. L. Lin; C. T. Chiou; L. K. Chen (Archives of Virology, 1998)

Induction of apoptosis and secondary necrosis by infectious pancreatic necrosis virus in fish embryonic cells - J‐R Hong; T‐L Lin; Y‐L Hsu; J‐L Wu (Journal of Fish Diseases, 1998)
Infectious pancreatic necrosis virus (IPNV) causes an acute, contagious disease in a number of economically important fish species (Pilcher & Fryer 1980). It is a member of the Birnaviridae (Brown 1986). In this study, the present authors first characterized the process of fish cell damage caused by IPNV infection in cultured cells, and found that it induced fragmentation of chromosomal DNA into oligonucleosomes and also caused nuclear fragmentation by secondary necrosis.

Fine mapping of quantitative trait loci Hd-1, Hd-2 and Hd-3, controlling heading date of rice, as single Mendelian factors - T. Yamamoto; Y. Kuboki; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

Mapping quantitative trait loci controlling seed dormancy and heading date in rice, Oryza sativa L., using backcross inbred lines - S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

Phylogenetic analysis of Methanobrevibacter isolated from feces of humans and other animals - Chuzhao Lin; T. L. Miller (Archives of Microbiology, 1998)

Time-course expression of vascular endothelial growth factor as related to the development of the retinochoroidal vasculature in rats - Xianjin Yi; Lin-Chin Mai; Masanobu Uyama; D. T. W. Yew (Experimental Brain Research, 1998)

Mapping quantitative trait loci associated with regeneration ability of seed callus in rice, Oryza sativa L. - F. Taguchi-Shiobara; S. Y. Lin; K. Tanno; T. Komatsuda; M. Yano; T. Sasaki; S. Oka (Theoretical and Applied Genetics, 1997)

Molecular analysis of survival motor neuron (SMN) and neuronal apoptosis inhibitory protein (NAIP) genes of spinal muscular atrophy patients and their parents - J.-G. Chang; Yuh-Jyh Jong; Shuan-Pei Lin; Bing-Wen Soong; Chang-Hai Tsai; T.-Y. Yang; Chih-Peng Chang; Wen-Shin Wang (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Raman spectra of high-pressure polymorphs of SiO 2 at various temperatures - Lin-gun Liu; T. P. Mernagh; W. O. Hibberson (Physics and Chemistry of Minerals, 1997)

The acetylcholine releaser linopirdine increases parietal regional cerebral blood flow in Alzheimer's disease - Christopher H. van Dyck; C. Huie Lin; Rhonda Robinson; Janet Cellar; Eileen O. Smith; J. Craig Nelson; Amy F. T. Arnsten; Paul B. Hoffer (Psychopharmacology, 1997)

Bcl-2 blocks peroxynitrite-induced apoptosis in HL-60 cells, an association with reactive oxygen species - K.-T. Lin; J.-Y. Xue; P. Y.-K. Wong (Inflammation Research, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Phylogenetic analysis of feline immunodeficiency virus isolated from cats in Taiwan - G. Inada; T. Miyazawa; Y. Inoshima; M. Kohmoto; Y. Ikeda; C. -H. Liu; J. A. Lin; T. -F. Kou; T. Mikami (Archives of Virology, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

The epidemiology and surveillance of blood lead in Taiwan (R.O.C.): A report on the PRESS-BLL project - T.-N. Wu; Chen-Yang Shen; Saou-Hsing Liou; Guang-Yang Yang; K.-N. Ko; Show-Lin Chao; Chao-Chun Hsu; P.-Y. Chang (International Archives of Occupational and Environmental Health, 1997)

Fine mapping of the MLK-3 gene within 11q13 and its exclusion as the MEN1 susceptibility gene - N. J. Lassam; Zheng Lin; Michael G. Shennan; Anouk Courseaux; Bin T. Teh; Patrick Gaudray; Catharina Larsson (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Trace elements and lipid peroxidation in uremic patients on hemodialysis - T. H. Lin; J. G. Chen; J. M. Liaw; J. G. Juang (Biological Trace Element Research, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

Lead-catalyzed peroxidation of essential unsaturated fatty acid - S. J. Yiin; T. H. Lin (Biological Trace Element Research, 1995)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

Leucine interference in the production of water-soluble red Monascus pigments - T. F. Lin; A. L. Demain (Archives of Microbiology, 1994)

Leucine interference in the production of water-soluble red Monascus pigments - T. F. Lin; A. L. Demain (Archives of Microbiology, 1994)

Trace elements in hair of blackfoot disease - T. C. Pan; T. H. Lin; C. L. Tseng; M. H. Yang; C. W. Huang (Biological Trace Element Research, 1993)

Simultaneous determination of Zn, Cd, Pb, and Cu in urine of patients with blackfoot disease using anodic stripping voltammetry - T. C. Pan; C. J. Horng; S. R. Lin; T. H. Lin; C. W. Huang (Biological Trace Element Research, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Selectivity in metal uptake by stationary phase microbial populations - Eugene T. Premuzic; Mow Lin; Hong Li Zhu; Annette M. Gremme (Archives of Environmental Contamination and Toxicology, 1991)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Induced formation of chelating agents byPseudomonas aeruginosa grown in presence of thorium and uranium - E. T. Premuzic; A. J. Francis; M. Lin; J. Schubert (Archives of Environmental Contamination and Toxicology, 1985)

Acute hepatotoxicity of a tetrachlorobiphenyl?Changes in the hepatocyte ultrastructure and plasma membrane-bound enzymes - F. S. Lin; M. T. Hsia; J. R. Allen (Archives of Environmental Contamination and Toxicology, 1979)

Characterization of the size and charge heterogeneities of human leukocyte interferon populations - L. S. Lin; Marzenna Wiranowska-Stewart; T. Chudzio; W. E. Stewart (Archives of Virology, 1978)

Influence of insecticide exposure on thein vivo andin vitro metabolic activity of rats - T. Lin; H. W. Dorough (Archives of Environmental Contamination and Toxicology, 1974)